External preparation containing non-lamellar liquid crystal forming lipids

By using non-layer liquid crystals to form external agents that combine lipids with drugs, the problems of low absorption of drugs and difficulty in maintaining them on the surface of biological bodies in the prior art are solved, and the drug permeability and drug delivery effect are improved.

CN112770778BActive Publication Date: 2025-03-04FARNEX INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980058315.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-07
Filing Date
2019-09-09
Publication Date
2025-03-04
Estimated Expiration
2039-09-09

AI Technical Summary

Technical Problem

In the prior art, the percutaneous absorption formulation has low drug absorption and is difficult to maintain on the surface of the organism, which limits the permeability of the drug and the drug delivery effect.

Method used

Non-layered liquid crystal-forming lipids are combined with drugs to prepare external agents that can form liquid crystals. Through the form of patches, aerosols or liquid crystal precursors of this preparation, it is applied to the skin or mucosal surface to enhance the permeability and retention of the drug.

Benefits of technology

It significantly improves the skin or mucosal permeability of the drug and can be stably maintained on the surface of the organism, enhancing the effect and durability of the drug delivery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112770778B_ABST
    Figure CN112770778B_ABST
Patent Text Reader

Abstract

The present invention relates to an external preparation which can be well retained on the surface of a living body and can increase drug permeability, and in particular to an external preparation containing a non-lamellar liquid crystal forming lipid and a drug.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an external preparation containing non-lamellar liquid crystal forming lipids. Background Art

[0002] Percutaneous absorption preparations used by attaching to the skin have advantages such as simplicity of administration and sustained release, and are increasingly used not only for local administration of various drugs but also for systemic administration. However, the skin has the function of limiting the permeation of substances as a biological barrier, and therefore, the drug absorbability in known percutaneous absorption preparations is basically low. Therefore, in order to promote the skin permeation of drugs, various percutaneous absorption enhancers are used in percutaneous absorption preparations, but the percutaneous absorption enhancement effect obtained is not necessarily sufficient.

[0003] There have been many reports on the usefulness of lyotropic liquid crystals such as liposomes as drug delivery systems (DDS) carriers that mimic biological entities since the concept of DDS was first proposed. In recent years, non-lamellar liquid crystals (NLLCs), a type of lyotropic liquid crystals, have been reported to have advantages such as higher drug content, easier preparation, and higher stability in polymer drugs compared to conventional DDS carriers.

[0004] Various liquid crystal forming compounds are used in various applications such as the cosmetics field and the pharmaceutical field. In recent years, lipid compounds that form cubic liquid crystals and show high stability even at low temperatures (below 6°C) have been developed, and the use of these liquid crystals in sustained-release preparations has been reported (Patent Document 1). However, these lipid compounds have high viscosity and cannot pass through fine syringe needles (e.g., 30Gage), making them difficult to use in injections. Therefore, lipid compounds that can stably form non-lamellar liquid crystals and have lower viscosity have been developed as bases for injections (Patent Document 2). Although Patent Document 3 discloses a skin topical preparation containing liquid crystals formed by this low-viscosity lipid compound, its main dosage forms are lotions and emulsions, and the skin retention is not high. In addition, Patent Document 3 does not record the application of this topical preparation to tissues other than the skin.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2006 / 043705

[0008] Patent Document 2: International Publication No. 2011 / 078383

[0009] Patent Document 3: Japanese Patent Application Publication No. 2012-17318 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The problem to be solved by the present invention is to provide an external preparation that can be well retained on the surface of a living body and can increase drug permeability.

[0012] Technical solutions to the problem

[0013] The present inventors conducted intensive research to solve the above-mentioned problems and found that when non-lamellar liquid crystal-forming lipids are used to manufacture preparations such as rubber patches, aerosol preparations, liquid crystal precursor preparations, etc., the results can achieve good preparation retention on the surface of the biological body and increase drug permeability. In addition, such preparations can be applied not only to the skin but also to mucous membranes, thereby completing the present invention.

[0014] That is, the present invention includes the following contents:

[0015] [1] An external preparation comprising a non-lamellar liquid crystal-forming lipid and a drug.

[0016] [2] The external preparation according to [1] above, which is an amphiphilic compound represented by the following general formula (I) or a salt thereof,

[0017] [Chemistry 1]

[0018]

[0019] In the formula, X and Y each represent a hydrogen atom or together represent an oxygen atom, n represents an integer of 0 to 2, m represents 1 or 2,

[0020]

[0021] represents a single bond or a double bond, and R represents a hydrophilic group having two or more hydroxyl groups.

[0022] [3] The external preparation according to the above [2], wherein R in the formula represents a hydrophilic group obtained by removing one hydroxyl group from any one selected from the group consisting of glycerol, erythritol, pentaerythritol, diglycerol, glyceric acid, triglycerol, xylose, sorbitol, ascorbic acid, glucose, galactose, mannose, dipentaerythritol, maltose, mannitol and xylitol.

[0023] [4] The external preparation according to any one of [1] to [3] above, wherein the non-lamellar liquid crystal forming lipid is mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol or mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol.

[0024] [5] The external preparation according to [1] above, wherein the non-lamellar liquid crystal-forming lipid is glyceryl monooleate or phytantriol.

[0025] [6] The external preparation according to any one of [1] to [5] above, which is formulated into a patch dosage form.

[0026] [7] The external preparation according to [6] above, wherein the patch is a rubber patch.

[0027] [8] The external preparation according to [6] or [7] above, which contains 70 w / w% or more of an adhesive.

[0028] [9] The external preparation according to any one of [1] to [5] above, which is formulated into an aerosol dosage form.

[0029]

[10] The external preparation according to any one of [1] to [9] above, wherein the non-lamellar liquid crystal-forming lipid does not form liquid crystals in the external preparation.

[0030]

[11] The external preparation according to any one of [1] to

[10] above, which is applied to a mucous membrane.

[0031]

[12] The external preparation according to any one of [1] to

[11] above, further comprising a water-soluble polymer and / or an oily component.

[0032]

[13] The external preparation according to

[12] above, wherein the water-soluble polymer is hydroxypropyl cellulose.

[0033]

[14] The external preparation according to any one of [1] to

[13] above, further comprising ethanol.

[0034]

[15] The external preparation according to any one of [1] to [5] above, comprising microparticles containing the non-lamellar liquid crystal-forming lipid and the drug.

[0035]

[16] The external preparation according to any one of [1] to

[15] above, which is used for drug delivery in the brain.

[0036] This specification includes the contents disclosed in Japanese Patent Application No. 2018-168365 which is the basis of priority of this application.

[0037] Effects of the Invention

[0038] According to the present invention, an external preparation can be provided, which can be well retained on the surface of a living body and can increase the drug skin permeability. In addition, according to the present invention, an external preparation can be provided, which can be applied to a mucosa and has a high drug mucosal permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1The photographs show images observed under a polarizing microscope. A: Preparation No. 1; B: Preparation No. 2; C: Preparation No. 3; D: Preparation No. 4; E: Preparation No. 5; F: Preparation No. 19; G: Preparation No. 25; H: Preparation No. 26.

[0040] Figure 2 The graphs show the results of small-angle X-ray diffraction: A: Preparation No. 1; B: Preparation No. 2; C: Preparation No. 3; D: Preparation No. 13, E: Preparation No. 25; F: Preparation No. 26; G: Preparation No. 27.

[0041] Figure 3 The graphs show the results of small-angle X-ray diffraction: A: Preparation No. 37; B: Preparation No. 45; C: Preparation No. 46; D: Preparation No. 47; E: Preparation No. 48; and F: Preparation No. 49.

[0042] Figure 4 is a schematic diagram of the vertical diffusion unit structure.

[0043] Figure 5 This is a graph showing the skin permeation behavior of FL-Na from a liquid crystal precursor preparation.

[0044] Figure 6 The graphs show the results of small-angle X-ray diffraction: A: Preparation No. 52 (water added), B: Preparation No. 53 (water added), C: Preparation No. 56 (water added), D: Preparation No. 57 (water added), and E: Preparation No. 56 (no water added).

[0045] Figure 7 This is a graph showing the skin permeation behavior of FL-Na from the spray. Each value is mean ± standard error (SE).

[0046] Figure 8 Schematic diagram showing the extension of the adhesive layer on the backing. The arrow indicates the extension direction of the adhesive layer.

[0047] Fig. 9 The following are photos showing phase images of the adhesive layer surface of the rubber patch preparations. A: Preparation No. 73, observation field 1μm×1μm; B: Preparation No. 63, observation field 1μm×1μm; C: Preparation No. 73, observation field 0.5μm×0.5μm; D: Preparation No. 63, observation field 0.5μm×0.5μm.

[0048] Fig.10 It is a schematic diagram of the horizontal diffusion unit structure.

[0049] Fig.11 It is a graph showing the release behavior of FL-Na from the rubber patch preparation.

[0050] Fig.12This is a graph showing the skin permeation behavior of FL-Na from a rubber patch preparation.

[0051] Fig.13 The graphs show the results of small-angle X-ray diffraction: A: Preparation No. 75; B: Preparation No. 76; C: Preparation No. 77.

[0052] Fig.14 It is a graph showing the release behavior of Tranilast from each preparation within 8 hours after application. Each value represents the mean ± standard error (SE). White squares represent preparation No. 75; black squares represent preparation No. 76; white triangles represent preparation No. 78.

[0053] Fig.15 It is a graph showing the time-dependent change of tranilast concentration in plasma within 8 hours after intranasal administration. Each value represents mean ± standard error (SE). White squares represent preparation No. 75; black squares represent preparation No. 76; white circles represent preparation No. 77; and white triangles represent preparation No. 78.

[0054] Fig.16 It is a graph showing the temporal changes of the concentration of tranilast in the brain within 8 hours after intranasal administration. Each value represents the mean ± standard error (SE). White squares represent preparation No. 75; black squares represent preparation No. 76; white circles represent preparation No. 77; and white triangles represent preparation No. 78.

[0055] Fig.17 It is a graph showing the concentration of tranilast in different regions of the brain 2 hours, 4 hours and 8 hours after intranasal administration. A: midbrain; B: cortex; C: cerebellum; D: hippocampus.

[0056] Fig.18 It is a graph showing the concentration of tranilast in different regions of the brain 2 hours, 4 hours and 8 hours after intranasal administration. A: spinal cord; B: olfactory bulb. DETAILED DESCRIPTION

[0057] Next, the present invention will be described in detail.

[0058] The present invention relates to an external preparation containing non-lamellar liquid crystal forming lipids and a drug. In the present invention, the external preparation refers to a drug applied to the surface of a living body (skin or mucous membrane, etc.) for the purpose of administering the drug. The external preparation may be a pharmaceutical composition. The external preparation of the present invention has biological surface adhesion, and is preferably stably maintained on the surface of the living body. If the external preparation of the present invention is applied to the surface of the living body, the drug is released from the liquid crystal formed by the non-lamellar liquid crystal forming lipid in the external preparation, and the drug effectively penetrates the skin and mucous membrane, etc. and is absorbed (administered) in the body. The external preparation of the present invention can significantly promote the penetration of drugs through the skin and mucous membrane, etc.

[0059] 1. Non-lamellar liquid crystal forming lipids

[0060] In the present invention, a lipid capable of forming non-lamellar liquid crystals (non-lamellar liquid crystal forming lipids) can be used as liquid crystal forming lipids. The non-lamellar liquid crystal forming lipids used in the present invention are preferably low molecular weight amphiphilic compounds. Here, "low molecular weight" refers to a molecular weight of about 20 to 10,000. The molecular weight of the non-lamellar liquid crystal forming lipids used in the present invention is preferably 50 to 5,000, more preferably 100 to 2,500, and further preferably 200 to 1,000.

[0061] In one embodiment, an amphiphilic compound represented by the following general formula (I) or a salt thereof can be used as the non-lamellar liquid crystal forming lipid.

[0062] [Chemistry 2]

[0063]

[0064] In the general formula (I), X and Y each represent a hydrogen atom or together represent an oxygen atom. In the general formula (I), n represents an integer of 0 to 2 (preferably 1 or 2), and m represents 1 or 2. In the amphiphilic compound represented by the general formula (I), the combination of n and m is any one of the following: n=0, m=1; n=0, m=2; n=1, m=1; n=1, m=2; n=2, m=1; or n=2, m=2.

[0065] In the formula:

[0066]

[0067] Indicates a single bond or a double bond.

[0068] R in the general formula (I) represents a hydrophilic group having two or more hydroxyl groups, and is not limited to the following, but for example, it can be mentioned: a hydrophilic group obtained by removing one hydroxyl group (OH) from any one selected from glycerol, erythritol, pentaerythritol, diglycerol, glyceric acid, triglycerol, xylose, sorbitol, ascorbic acid, glucose, galactose, mannose, dipentaerythritol, maltose, mannitol and xylitol. R in the general formula (I) is more preferably a hydrophilic group obtained by removing one hydroxyl group (OH) from glycerol, pentaerythritol, erythritol, diglycerol, glyceric acid or xylose, and is particularly preferably a hydrophilic group obtained by removing one hydroxyl group (OH) from glycerol. It should be noted that the hydrophilic group obtained by removing one hydroxyl group (OH) from glyceric acid may be a hydrophilic group obtained by removing the OH (hydroxyl group) contained in the carboxyl group of glyceric acid.

[0069] It should be noted that in the present invention, the expression in the general formula (I):

[0070]

[0071] This means that the amphiphilic compound is an E-isomer (cis-isomer) or a Z-isomer (trans-isomer) of a geometric isomer or a mixture thereof. The meaning of this expression is the same also in the general formulae (II) and (III) described below.

[0072] Examples of the amphiphilic compound represented by the general formula (I) include amphiphilic compounds represented by the following general formula (II).

[0073] [Chemistry 3]

[0074]

[0075] In the general formula (II), X and Y each represent a hydrogen atom or together represent an oxygen atom, n represents an integer of 0 to 2 (0, 1 or 2), and m represents 1 or 2.

[0076] R in the general formula (II) represents a hydrophilic group obtained by removing one hydroxyl group (OH) from any one selected from glycerol, erythritol, pentaerythritol, diglycerol, glyceric acid, triglycerol, xylose, sorbitol, ascorbic acid, glucose, galactose, mannose, dipentaerythritol, maltose, mannitol and xylitol. A preferred example of R is a hydrophilic group obtained by removing one hydroxyl group (OH) from any one selected from glycerol, pentaerythritol, erythritol, diglycerol, glyceric acid and xylose, and more preferably a hydrophilic group obtained by removing one hydroxyl group (OH) from glycerol. The hydrophilic group obtained by removing one hydroxyl group (OH) from glyceric acid may be a hydrophilic group obtained by removing the OH (hydroxyl group) contained in the carboxyl group of glyceric acid.

[0077] Other examples of the amphiphilic compound represented by the general formula (I) include amphiphilic compounds represented by the following general formula (III).

[0078] [Chemistry 4]

[0079]

[0080] In the general formula (III), X and Y each represent a hydrogen atom or together represent an oxygen atom, n represents an integer of 0 to 2 (preferably 1 or 2), and m represents 1 or 2.

[0081] R in the general formula (III) represents a hydrophilic group having two or more hydroxyl groups, and is not limited to the following, but for example, it can be mentioned: a hydrophilic group obtained by removing one hydroxyl group (OH) from any one selected from glycerol, erythritol, pentaerythritol, diglycerol, glyceric acid, triglycerol, xylose, sorbitol, ascorbic acid, glucose, galactose, mannose, dipentaerythritol, maltose, mannitol and xylitol. A preferred example of R is a hydrophilic group obtained by removing one hydroxyl group (OH) from any one selected from glycerol, pentaerythritol, erythritol, diglycerol, glyceric acid and xylose, and more preferably a hydrophilic group obtained by removing one hydroxyl group (OH) from glycerol. The hydrophilic group obtained by removing one hydroxyl group (OH) from glyceric acid can be a hydrophilic group obtained by removing the OH (hydroxyl group) contained in the carboxyl group of glyceric acid.

[0082] As another example of the amphiphilic compound represented by the general formula (I), there can be mentioned an amphiphilic compound represented by the following general formula (IV).

[0083] [Chemistry 5]

[0084]

[0085] In the general formula (IV), X and Y each represent a hydrogen atom or together represent an oxygen atom, n represents an integer of 0 to 2 (preferably 1 or 2), and m represents 1 or 2.

[0086] R in the general formula (IV) represents a hydrophilic group having two or more hydroxyl groups, and is not limited to the following, but for example, it can be mentioned: a hydrophilic group obtained by removing one hydroxyl group (OH) from any one of glycerol, erythritol, pentaerythritol, diglycerol, glyceric acid, triglycerol, xylose, sorbitol, ascorbic acid, glucose, galactose, mannose, dipentaerythritol, maltose, mannitol and xylitol. A preferred example of R is a hydrophilic group obtained by removing one hydroxyl group (OH) from any one selected from glycerol, pentaerythritol, erythritol, diglycerol, glyceric acid and xylose, and more preferably a hydrophilic group obtained by removing one hydroxyl group (OH) from glycerol. The hydrophilic group obtained by removing one hydroxyl group (OH) from glyceric acid can be a hydrophilic group obtained by removing the OH (hydroxyl group) contained in the carboxyl group of glyceric acid.

[0087] Preferred examples of the amphiphilic compound represented by the general formula (I) include:

[0088] Mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol,

[0089] Mono-O-(5,9,13-trimethyltetradecanoyl)glycerol,

[0090] Mono-O-(5,9,13-trimethyltetradecano-4,8.12-trienoyl)glycerol,

[0091] Mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol,

[0092] Mono-O-(5,9,13,17-tetramethyloctadecanoyl)glycerol, and

[0093] Mono-O-(5,9,13,17-tetramethyloctadec-4,8,12,16-tetraenoyl)glycerol,

[0094] However, the invention is not limited to these.

[0095] As further preferred examples, mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol and mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol can be mentioned.

[0096] The amphiphilic compound represented by the general formula (I) used in the present invention shows high stability under a wide range of environmental conditions. For example, the amphiphilic compound represented by the general formula (I) is characterized in that it has an isoprenoid chain as a hydrophobic group, which is different from the amphiphilic compound having a straight fatty chain such as oleic acid as a hydrophobic group, and has high resistance to hydrolysis and high oxidative stability. In addition, the amphiphilic compound represented by the general formula (I) has a wide temperature range for obtaining liquid crystals, a low Krafft temperature, and can stably form liquid crystals even at low temperatures (below 6°C, preferably 0°C or below).

[0097] In addition, the amphiphilic compound represented by the general formula (I) used in the present invention itself shows a low viscosity. Specifically, the amphiphilic compound represented by the general formula (I) itself preferably has a viscosity of 15.0 Pa·s or less, more preferably 11.0 Pa·s or less, and further preferably 6.0 Pa·s or less in the measured value at 25°C. The viscosity can be measured, for example, at a temperature of 25°C using a viscosity / viscoelasticity measuring device (Gemini II, Malvern).

[0098] The external preparation of the present invention may contain a salt of the amphiphilic compound represented by the general formula (I). The salt of the amphiphilic compound represented by the general formula (I) of the present invention may be any salt, including salts of alkali metals or alkaline earth metals such as sodium, potassium, calcium, and magnesium, preferably sodium salts and potassium salts. The salt of the amphiphilic compound represented by the general formula (I) of the present invention may be a pharmaceutically acceptable salt or a cosmetically acceptable salt.

[0099] The present invention is not limited to the external preparation using the amphiphilic compound represented by the general formula (I) or a salt thereof, and any other non-lamellar liquid crystal-forming lipid may be used.

[0100] The non-lamellar liquid crystal forming lipid used in the present invention may be, for example, a glycerol fatty acid monoester. As the fatty acid constituting the glycerol fatty acid monoester, a saturated or unsaturated fatty acid having 8 to 24 carbon atoms is preferred. As other examples of glycerol fatty acid monoesters, glycerol monooleate (GMO; also known as: glyceryl monooleate), glycerol monoisostearate, glycerol monoreversible oleate (グリセリルモノエライジレート), etc. may be cited, but are not limited to these. Alternatively, as a non-lamellar liquid crystal forming lipid, a glycerol monoalkyl ether may also be used. As a glycerol monoalkyl ether, specifically, glycerol monooleyl ether (also known as: oleic acid glyceryl), glycerol monoisostearyl ether (also known as: isostearic acid glyceryl), glycerol monoreversible oleate (グリセリンモノエライジルエーテル), etc. may be cited, but are not limited to these. Furthermore, as other non-lamellar liquid crystal-forming lipids, phytantriol (PHY) and the like can be used.

[0101] The non-lamellar liquid crystal forming lipid used in the present invention also includes a combination of two or more lipids that form non-lamellar liquid crystals by mixing, and a lipid that forms non-lamellar liquid crystals by combining with an oily component, etc. Such non-lamellar liquid crystal forming lipids are known to those skilled in the art.

[0102] By adding one or more predetermined components such as an oily component to the non-lamellar liquid crystal-forming lipid used in the present invention, the formed liquid crystal structure may be changed. When an external preparation contains a non-lamellar liquid crystal-forming lipid and such a component, even when the liquid crystal structure changes compared to a case where the component is not contained, as long as non-lamellar liquid crystals are formed after the liquid crystal structure changes, the external preparation and the non-lamellar liquid crystal-forming lipid used in the external preparation are also included in the scope of the "external preparation" and "non-lamellar liquid crystal-forming lipid" in the present invention, respectively.

[0103] The non-lamellar liquid crystal forming lipid used in the present invention can form non-lamellar liquid crystals in an aqueous medium (aqueous phase). It should be noted that, in the present invention, an aqueous medium containing non-lamellar liquid crystal forming lipids is sometimes referred to as a "non-lamellar liquid crystal forming lipid / aqueous system" or "amphiphilic compound / aqueous system".

[0104] The non-lamellar liquid crystal forming lipid contained in the external preparation of the present invention forms a non-lamellar liquid crystal in the external preparation, or forms a non-lamellar liquid crystal on the surface of the organism due to the presence of surrounding water when applied to the surface of the organism, or forms a non-lamellar liquid crystal on the surface of the organism due to the volatilization of volatile components (solvents such as ethanol, propellants, etc.) when applied to the surface of the organism. The non-lamellar liquid crystal formed by the non-lamellar liquid crystal forming lipid contained in the external preparation of the present invention is preferably a type II (water-in-oil) liquid crystal in which the hydrophobic group is oriented outward, more preferably a cubic liquid crystal, an inverted hexagonal liquid crystal, or a mixed system thereof, but is not limited to these.

[0105] The analysis of the liquid crystal structure formed by the non-lamellar liquid crystal-forming lipids can be performed by conventional methods such as observation using a polarizing microscope or small-angle X-ray scattering (SAXS) measurement.

[0106] For example, in order to confirm the formation of liquid crystals, various liquid crystal structures can also be studied by small angle X-ray scattering (SAXS). Generally, a non-lamellar liquid crystal forming lipid / aqueous system sample of a predetermined concentration is first added to, for example, a quartz X-ray capillary, and then the capillary is sealed with an oxygen burner and subjected to SAXS measurement.

[0107] The formation of liquid crystal can be confirmed by confirming the results of SAXS measurement and whether the following ratios (peak intervals) of scattering peaks that are unique to each liquid crystal structure are present.

[0108] Ratio of Pn3m cubic liquid crystal:

[0109]

[0110] Ratio of Ia3d cubic liquid crystal:

[0111]

[0112] Ratios of Im3m cubic liquid crystal:

[0113]

[0114] Ratios of Fd3m cubic liquid crystal:

[0115]

[0116] Ratios unique to inverse hexagonal liquid crystals:

[0117]

[0118] By a method well known to those skilled in the art, if the peak values ​​are calculated from the SAXS data and the ratio of their reciprocals is then obtained, the space group and the lattice constant can be easily determined.

[0119] The amphiphilic compound represented by the general formula (I) used in the external preparation of the present invention can be synthesized by referring to the description of the examples described below or by the synthesis method described in the international publication WO2014 / 178256. Alternatively, the amphiphilic compound represented by the general formula (III) can be synthesized by the synthesis method described in the international publication WO2011 / 078383, for example. Furthermore, the amphiphilic compound represented by the general formula (IV) can be synthesized by the synthesis method described in the international publication WO2006 / 043705, for example.

[0120] It is preferred to confirm in advance that the synthesized compound is the target compound by a conventional method such as nuclear magnetic resonance (NMR) measurement.

[0121] In addition, various other non-lamellar liquid crystal lipids are commercially available. Glyceryl monooleate (GMO) and phytantriol (PHY) are commercially available from Tokyo Chemical Industry Co., Ltd., Kao Corporation, Riken Vitamin Co., Ltd. (all Japan), etc. Oleic acid glyceryl ester is commercially available from Nikko Chemical Co., Ltd. (Japan) as a trade name NIKKOL Selachyl Alcohol V, for example. Isostearic acid glyceryl ester is commercially available from Kao Corporation (Japan) as a trade name Penetol GE-IS, for example.

[0122] The external preparation of the present invention contains an effective amount of non-lamellar liquid crystal forming lipids. The amount of non-lamellar liquid crystal forming lipids contained in the external preparation of the present invention is not limited to the following, but can generally be 0.1 w / w% or more, 0.5 w / w% or more, for example, 3 w / w% or more, 5 w / w% or more, 0.5 w / w% to 99.8 w / w%, 1 w / w% to 99.5 w / w%, 5 w / w% to 99 w / w%, 10 w / w% to 99.8 w / w%, 40 w / w% to 99.8 w / w%, 60 w / w% or more, 70 w / w% or more, or 100 w / w% to 99.8 w / w%. / w% or above, 60w / w%~99.8w / w%, 65w / w%~99.8w / w%, 68w / w%~99w / w%, 70w / w%~99.5w / w%, 70w / w%~90w / w%, 10w / w %~30w / w%, 10w / w%~25w / w%, 13w / w%~15w / w%, 3w / w%~20w / w%, 3w / w%~15w / w%, 3w / w%~10w / w% or 5w / w%~9w / w%.

[0123] The "total weight of the external preparation" mentioned here refers to the total weight of a composition (preferably a mixed or dispersed composition) containing at least non-lamellar liquid crystal-forming lipids and a drug for use as an external preparation. The weight of other components such as the support for the composition and the container for containing the composition are not included in the "total weight".

[0124] 2. Medication

[0125] The drug mixed in the topical preparation of the present invention is released to the surface of the organism by applying the topical preparation to the surface of the organism, and is absorbed into the body through the skin and mucous membranes. The drug can be any substance (active ingredient) to be administered to the organism. However, the drug is not a non-lamellar liquid crystal-forming lipid itself. The drug can be an organic compound or an inorganic compound. The drug can be a water-soluble drug or a fat-soluble (lipophilic, water-insoluble or poorly water-soluble) drug. The drug can be a physiologically active substance. The drug can be, for example, a protein, a peptide, an amino acid, a nucleic acid, etc., but is not limited to these. The drug may be, for example, an anticancer agent, an immunosuppressant, an analgesic (e.g., non-opioid analgesics, opioid analgesics such as morphine), an anti-inflammatory agent, an antiallergic agent (such as Tranilast), a steroid drug (such as triamcinolone acetonide), an anti-obesity drug, an anti-diabetic drug, an antibiotic, an antifungal agent, an antiviral agent, a vasodilator, an anesthetic, a smoking cessation aid (such as nicotine), an antipsychotic, a hypotensive drug, a cardiotonic, a beta-blocker, an anemic agent, an antihyperlipidemic agent, a bronchodilator, a dementia treatment drug, a drug for treating central nervous system diseases such as Alzheimer's disease, Parkinson's disease, cerebrovascular disorders or brain tumors, a drug for treating chronic obstructive pulmonary disease (COPD), a drug for treating glaucoma, a drug for treating cataracts, a drug for treating age-related macular degeneration, a drug for treating overactive bladder, a drug for treating attention deficit hyperactivity disorder, a hormone agent, a vaccine, etc., but is not limited to these.

[0126] 3. Dosage form and composition of topical preparations

[0127] The topical preparation of the present invention can be used for systemic administration or for local administration. The topical preparation of the present invention can be formulated into any dosage form. The topical preparation of the present invention is not limited to the following, but may have: patches, such as rubber patches (also known as plasters), gel patches, etc.; sprays, such as aerosols, pump sprays (manual or powered sprays), etc.; ointments, creams, oral preparations, nasal preparations, suppositories, vaginal preparations and other dosage forms. Sprays refer to pharmaceutical preparations in which the drug is sprayed by applying pressure by hand, power, propellant (gas) or any other means. The topical preparation of the present invention may contain microparticles, which contain non-lamellar liquid crystal forming lipids and drugs (e.g., microparticles or nanoparticles). The topical preparation of the present invention may also be a dispersion, for example, it may be a dispersion containing the microparticles (e.g., microparticles or nanoparticles). The present invention also provides preparations of any dosage form containing the topical preparation of the present invention.

[0128] The topical preparation of the present invention can be used on the surface of a living body, preferably applied to the skin (skin surface). Or the topical preparation of the present invention is used to be applied to a mucous membrane (mucous membrane surface). The topical preparation of the present invention can promote drug penetration through the skin or mucous membrane. The topical preparation of the present invention is not only applied to the skin, but also applied to mucous membrane.

[0129] As other components, the topical preparation of the present invention may contain an aqueous medium. As an aqueous medium, it is not limited to the following, but can be water such as sterile water, purified water, distilled water, ion exchange water, ultrapure water; electrolyte aqueous solutions such as physiological saline, sodium chloride aqueous solution, calcium chloride aqueous solution, magnesium chloride aqueous solution, sodium sulfate aqueous solution, potassium sulfate aqueous solution, sodium carbonate aqueous solution, sodium acetate aqueous solution; buffer solutions such as phosphate buffer or Tris-hydrochloric acid buffer, etc. The aqueous medium is preferably physiologically acceptable water or aqueous solution. The aqueous medium can be, for example, a component of an topical preparation such as a drug that is dissolved, dispersed or suspended.

[0130] As other ingredients, the external preparation of the present invention may contain a water-soluble polymer. Examples of the water-soluble polymer include hydroxypropyl cellulose (HPC), hydroxyethyl cellulose, polyvinyl pyrrolidone, carbon black, carrageenan, chitosan, chondroitin sulfate, xanthan gum, hyaluronate (sodium hyaluronate, etc.), alginate (sodium alginate, etc.), gelatin, dextran, etc., but are not limited to these. Examples of hydroxypropyl cellulose (HPC) include five grades of HPC sold by Nippon Soda Co., Ltd. (Japan): HPC-SSL (molecular weight of about 40,000, viscosity of 2 to 2.9 mPa·s), HPC-SL (molecular weight of about 100,000, viscosity of 3 to 5.9 mPa·s), HPC-L (molecular weight of about 140,000, viscosity of 6 to 10 mPa·s), HPC-M (molecular weight of about 620,000, viscosity of 150 to 400 mPa·s), and HPC-H (molecular weight of about 910,000, viscosity of 1000 to 4000 mPa·s). In one embodiment, the molecular weight of the hydroxypropyl cellulose may be 1000,000 or less or 800,000 or less, for example, 10,000 to 700,000 or 10,000 to 80,000.

[0131] The amount of the drug contained in the external preparation of the present invention is not limited to the following, but can generally be 0.0001w / w% or more relative to the total weight of the external preparation, for example, 0.0001w / w% to 10w / w%, 0.0005w / w% to 5w / w%, 0.0005w / w% to 1w / w%, 0.001w / w% to 5w / w%, 0.001w / w% to 1w / w%, w%, 0.001w / w% to 0.1w / w%, 0.001w / w% to 0.05w / w%, 0.001w / w% to 0.01w / w%, 0.01w / w% to 5w / w%, 0.01w / w% to 1w / w%, 0.01w / w% to 0.1w / w%, 0.05w / w% to 1w / w% or 0.1w / w% to 0.5w / w%. The meaning of "total weight of external preparation" is as described above. It should be noted that, with respect to the present invention, w / w% means weight / weight%, and can be used interchangeably with mass / mass%.

[0132] As other components, the external preparation of the present invention may contain an oily component. The oily component is not limited to the following, but examples thereof include: hydrocarbon oil, ester oil; fats and oils such as vegetable oil and animal oil; higher alcohols such as behenyl alcohol and stearyl alcohol; higher fatty acids such as stearic acid and palmitic acid; fat-soluble vitamins, etc. Specific examples of the oily component include: squalene, squalane, isopropyl myristate, octyldodecyl myristate, castor oil, olive oil, tocopherol, and tocopherol acetate, etc., but are not limited to these.

[0133] As other ingredients, the topical preparation of the present invention may contain a surfactant. Examples of surfactants used in the present invention include: block copolymers formed by hydrophilic ethylene oxide and hydrophobic propylene oxide (polyoxyethylene polyoxypropylene glycol), polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, and nonionic surfactants represented by polyoxyethylene hydrogenated castor oil. As nonionic surfactants, a molecular weight of 1000 or more (more preferably 5000 or more) is more preferred. Block copolymers formed by ethylene oxide and propylene oxide include: polyoxyethylene (200) polyoxypropylene (70) glycol, polyoxyethylene (196) polyoxypropylene (67) glycol, polyoxyethylene (160) polyoxypropylene (30) glycol, polyoxyethylene (120) polyoxypropylene (40) glycol, etc. These block copolymers formed by ethylene oxide and propylene oxide are represented by Pluronic (R) , Poloxamer (R) 、UNILUBE (R) ,PLONON (R)Particularly preferred examples of surfactants include polyoxyethylene (200) polyoxypropylene (70) glycol, polyoxyethylene (196) polyoxypropylene (67) glycol (also known as Pluronic (R) F127; UNILUBE 70DP-950B, Poloxamer (R) 407), etc., but are not limited to these. It should be noted that in the present invention, the non-lamellar liquid crystal forming lipid used in the present invention is not included in the scope of the surfactant. The external preparation of the present invention may contain one or more of such surfactants.

[0134] Relative to the total weight of the external preparation, the surfactant of the external preparation of the present invention can generally contain 0.001w / w% or more, for example, 0.01w / w% or more, preferably 0.05w / w% or more, more preferably 0.1w / w% or more, for example, 0.01w / w% to 10w / w%, 0.1w / w% to 5w / w%, 0.3w / w% or more, 0.3w / w% to 2w / w%, 0.3w / w% to 1.5w / w%, 0.3w / w% to 1w / w% or 0.55w / w% to 0.9w / w%.

[0135] The external preparation of the present invention may contain ethanol (in the present invention, unless otherwise specified, it refers to anhydrous ethanol) as another component. It should be noted that ethanol (anhydrous ethanol) is not an aqueous medium.

[0136] The external preparation of the present invention may contain, as other ingredients, a pharmaceutically acceptable water-soluble organic compound such as propylene glycol, glycerin, ethylene glycol, or butylene glycol.

[0137] As other components, the external preparation of the present invention may contain other pharmaceutically acceptable additives, such as carriers, excipients, stabilizers, buffers, preservatives, colorants, flavoring agents, pH adjusters, dispersants, etc., but are not limited thereto.

[0138] In the topical preparation of the present invention, the non-lamellar liquid crystal forming lipid may or may not form a liquid crystal (particularly a non-lamellar liquid crystal). When the non-lamellar liquid crystal forming lipid does not form a liquid crystal in the topical preparation, the topical preparation is also referred to as a liquid crystal precursor preparation. In the topical preparation of the present invention that does not contain an aqueous medium or does not contain a sufficient amount of an aqueous medium, since the non-lamellar liquid crystal forming lipid does not form a liquid crystal, the topical preparation is a liquid crystal precursor preparation.

[0139] By applying the topical preparation of the present invention to the surface of an organism, preferably to the skin or mucosa, the drug contained in the topical preparation can be administered to the organism. The present invention also provides a drug delivery method or a drug administration method, which includes applying the topical preparation of the present invention to the surface of an organism, preferably to the skin or mucosa. The application object of the topical preparation of the present invention is not particularly limited, but is generally an animal, preferably a primate including humans; livestock; pets such as dogs, cats, rabbits, experimental animals, etc., including mammals or birds.

[0140] Next, preferred dosage forms of the external preparation are described in detail.

[0141] 4. Patches

[0142] The topical preparation of the present invention can be formulated into the dosage form of a patch. The present invention also provides a patch containing the topical preparation of the present invention. In the present invention, a patch refers to a pharmaceutical preparation that is attached to the skin or mucous membrane and used for the purpose of percutaneous or permucosal absorption of drugs. The patch can be a local action type or a systemic action type. The patch has an adhesive layer. The adhesive layer of the patch is preferably a composition containing an adhesive (more preferably a fat-soluble adhesive), and in addition to the adhesive, it is also preferably containing non-lamellar liquid crystal forming lipids and drugs. As patches (patches), it is not limited to the following, but can be cited: rubber plasters (also referred to as: plasters), gel patches (cataplasms) and the like.

[0143] The rubber patch is a preparation having an adhesive layer formed by using a pressure-sensitive adhesive as a base. The adhesive layer is preferably a composition containing a pressure-sensitive adhesive, a non-lamellar liquid crystal forming lipid and a drug. In one embodiment, the rubber patch has an adhesive layer and a support, and the adhesive layer contains a pressure-sensitive adhesive, a non-lamellar liquid crystal forming lipid and a drug. In a preferred embodiment, the rubber patch is a so-called matrix-type preparation having an adhesive layer, a backing (release sheet) and a support, and the adhesive layer contains a pressure-sensitive adhesive, a non-lamellar liquid crystal forming lipid and a drug. The pressure-sensitive adhesive used for the rubber patch is preferably a fat-soluble polymer. As a pressure-sensitive adhesive, it is not limited to the following, but can be cited: acrylic, urethane, rubber, or silicone adhesives. As an acrylic adhesive, it is not limited to the following, but can be cited as DURO-TAK (R) (Henkel), such as DURO-TAK (R) 387-2516.

[0144] The support can be any shape that can be used in the patch, but is preferably a sheet-like substrate. As the support, for example, a known support can be used. The support can be, for example, any material suitable as a support for the patch, for example, a film such as a polymer film, a cloth such as a nonwoven or woven fabric, paper, etc. The support can be, for example, made of cellulose derivatives such as polyester, polyethylene (polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, etc.), polyolefins (polyethylene, polypropylene, etc.), cellulose esters, polyurethanes, polyamides, etc. The thickness of the support is not limited to the following, but is generally 5 μm to 500 μm, preferably 10 to 300 μm, for example, 10 to 200 μm, 10 to 100 μm, 25 to 100 μm, 50 μm to 300 μm or 60 μm to 200 μm.

[0145] As a peeling sheet, any peeling sheet that can be used in a patch can be used, for example, a known peeling film can be used. The peeling sheet can be composed of, for example, polyester (polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, etc.), polyolefin (polyethylene, polypropylene, etc.), polymer films such as polyvinyl chloride and polyvinylidene chloride, cellulose derivatives such as cellulose ester, or paper, etc., having layers such as fluororesin and silicone resin on the contact surface with the adhesive layer, or a laminated film using these various materials, etc. The thickness of the peeling sheet is not limited to the following, but is generally 5 to 500 μm, preferably 10 to 300 μm, for example, 10 to 200 μm, 25 to 100 μm, 50 μm to 300 μm, or 60 μm to 200 μm.

[0146] The thickness of the adhesive layer in the patch is not limited to the following, but is generally 5 μm to 1 mm, preferably 5 to 500 μm, for example, 5 to 200 μm, 10 to 100 μm, or 20 to 50 μm.

[0147] With regard to the non-lamellar liquid crystal forming lipids and drugs, as described above.

[0148] In one embodiment, the amount of non-lamellar liquid crystal forming lipids in the adhesive layer of a patch such as a rubber patch is preferably the amount of liquid crystal formation. About non-lamellar liquid crystal forming lipids, as described above. More specifically, the amount of non-lamellar liquid crystal forming lipids in the adhesive layer is not limited to the following, but relative to the gross weight of the adhesive layer, is usually 0.1w / w% or more, preferably 5w / w% or more, for example, 1w / w% to 20w / w%, 1w / w% to 10w / w%, 5w / w% to 20w / w%, 5w / w% to 10w / w%, 10w / w% to 30w / w%, 10w / w% to 25w / w% or 13w / w% to 15w / w%.

[0149] The amount of the drug in the adhesive layer is not limited to the following, but is generally 0.0001 w / w% or more, preferably 0.0005 w / w% to 5 w / w%, more preferably 0.001 w / w% to 5 w / w%, for example 0.001 w / w% to 1 w / w%, 0.01 w / w% to 1 w / w%, 0.05 w / w% to 1 w / w% or 0.1 to 0.5 w / w%, relative to the total weight of the adhesive layer.

[0150] The amount of adhesive (e.g., pressure-sensitive adhesive) in the adhesive layer is not limited to the following, but is generally 70 w / w% or more, preferably 75 w / w% or more, more preferably 75 w / w% to 90 w / w%, 75 w / w% to 85 w / w%, 80 w / w% to 95 w / w%, or 85 w / w% to 95 w / w%, 85 w / w% to 90 w / w%, for example 80 w / w% or 90 w / w%.

[0151] In one embodiment, the amount of non-lamellar liquid crystal forming lipid and adhesive in the adhesive layer of a patch such as a rubber patch is not limited to the following, but can be 1 w / w% to 20 w / w%, 75 w / w% to 90 w / w% respectively relative to the total weight of the adhesive layer. In another embodiment, the amount of non-lamellar liquid crystal forming lipid and adhesive in the adhesive layer of a patch such as a rubber patch is not limited to the following, but can be 1 w / w% to 10 w / w%, 85 w / w% to 95 w / w% respectively relative to the total weight of the adhesive layer. In another embodiment, the amount of non-lamellar liquid crystal forming lipid and adhesive in the adhesive layer of a patch such as a rubber patch is not limited to the following, but can be 10 w / w% to 15 w / w%, 75 w / w% to 85 w / w% respectively relative to the total weight of the adhesive layer. In another embodiment, the amount of non-lamellar liquid crystal forming lipids and adhesive in the adhesive layer of a patch such as a rubber patch is not limited to the following, but can be 13w / w% to 15w / w% and 75w / w% to 85w / w%, respectively, relative to the total weight of the adhesive layer.

[0152] When the adhesive layer of a patch such as a rubber patch contains non-lamellar liquid crystal formation lipid and medicine, it is preferably containing an aqueous medium (e.g., water). By containing an aqueous medium, non-lamellar liquid crystal formation lipid forms liquid crystal in the patch, and the medicine is encapsulated in the liquid crystal. About aqueous medium, as described above. Or, the patch itself may not contain an aqueous medium, in which case, when the patch is applied to the surface of an organism, non-lamellar liquid crystal formation lipid forms liquid crystal on the surface of the organism due to the presence of water around, and the medicine may also be encapsulated in the liquid crystal. In one embodiment, the aqueous medium, as the liquid containing medicine or other components, may be mixed in the adhesive layer composition. The amount of the aqueous medium in the adhesive layer is not limited to the following, but is generally 0.1 w / w% or more, preferably 0.5 w / w% or more, more preferably 1 w / w% or more, for example, 5 w / w% or more, 3 w / w% to 30 w / w%, 5 w / w% to 10 w / w%, 10 w / w% to 30 w / w%, 10 w / w% to 25 w / w%, or 13 w / w% to 15 w / w%. In one embodiment, the weight ratio of the non-lamellar liquid crystal forming lipid to the aqueous medium in the adhesive layer may preferably be 1:5 to 5:1, for example, 1:1 to 10:1, 1:1 to 5:1, 1:1 to 3:1, 1.5:1 to 10:1, 2:1 to 5:1, and in a preferred example, 2:1 to 3:1. The weight ratio of the non-lamellar liquid crystal-forming lipid to the adhesive in the adhesive layer may be, for example, 1:2 to 1:20, preferably 1:2 to 1:15, 1:3 to 1:10, 1:3 to 1:8 or 1:5 to 1:7.

[0153] The adhesive layer may further contain other components. The other components are as described above with respect to the external preparation of the present invention.

[0154] The manufacture of patch such as rubber plaster uses technology known to those skilled in the art. In one embodiment, non-lamellar liquid crystal is formed into lipid, medicine and aqueous medium, and other components are uniformly mixed to prepare liquid crystal gel according to the situation, then mixed adhesive to prepare adhesive layer composition, the adhesive layer composition is extended on backing, the adhesive layer is dried, the adhesive layer is crimped and fixed on support, and a certain size is cut as needed, thus patch such as rubber plaster can be manufactured. Alternatively, liquid crystal gel can also be prepared as described above, then mixed adhesive to prepare adhesive layer composition, the adhesive layer composition is coated on support, the adhesive layer is dried, then the backing is attached to the adhesive layer, and a certain size is cut as needed, thus patch such as rubber plaster is manufactured. Patch such as rubber plaster can be made with a size and / or shape suitable for being attached to the affected part, or it can be made with a predetermined size and / or shape, and is cut into appropriate size and / or shape when used for use.

[0155] In such patches such as rubber patches, drugs are introduced into liquid crystals formed by non-lamellar liquid crystal forming lipids, and if the patch is applied to biological surfaces such as skin and mucous membranes, it will play a role in increasing drug permeability in the skin and mucous membranes.

[0156] By applying the patch of the present invention, for example, a rubber plaster, to the biological surface of an object (for example, a mammal), preferably applied to skin or mucous membrane (attachment), the medicine contained in the patch can be administered to the object through the skin or through the mucosa. About the object, as described above. The present invention also provides the administration method or the delivery method of such a medicine.

[0157] 5. Aerosol

[0158] The topical preparation of the present invention can be formulated into an aerosol dosage form. The present invention also provides an aerosol containing the topical preparation of the present invention. The aerosol in the present invention refers to a pharmaceutical preparation in a dosage form in which the drug is sprayed out by the pressure of a propellant filled together with the drug in the same container. The topical preparation of the present invention formulated into an aerosol dosage form consists of a composition containing non-lamellar liquid crystal forming lipids and a drug and a propellant. Examples of propellants include: liquefied gas and / or compressed gas. As liquefied gas, for example, liquefied petroleum gas (LPG), dimethyl ether (DME), etc. As compressed gas, carbon dioxide, nitrogen, air, etc. can be mentioned. In the aerosol of the present invention, the propellant is more preferably liquefied gas, and LPG is further preferred.

[0159] The aerosol of the present invention is preferably filled with a composition and a propellant containing non-lamellar liquid crystal forming lipids and a drug in a container. The composition containing non-lamellar liquid crystal forming lipids and a drug is preferably liquid, preferably aqueous. In other words, the external preparation of the present invention formulated as an aerosol formulation preferably contains an aqueous medium in addition to non-lamellar liquid crystal forming lipids, drugs and propellants. By containing an aqueous medium, non-lamellar liquid crystal forming lipids form liquid crystals, and the drug is encapsulated in the liquid crystal. Alternatively, the external preparation of the present invention formulated as an aerosol formulation can contain an aqueous medium, but in this case, the non-lamellar liquid crystal forming lipids in the external preparation form form non-lamellar liquid crystals through an aqueous medium (for example, external moisture such as moisture in the body or added water) present in the application site, and the drug is encapsulated in the liquid crystal. If the aerosol of the present invention is applied to the surface of the organism, the volatile components (solvents such as ethanol, propellants, etc.) in the aerosol volatilize, and non-lamellar liquid crystals can be formed on the surface of the organism. In the aerosol of the present invention, the composition containing the non-lamellar liquid crystal-forming lipid and the drug and the propellant may be mixed in the container or separated into multiple phases. The non-lamellar liquid crystal-forming lipid, the drug, and the aqueous medium are as described above.

[0160] In one embodiment, the amount of non-lamellar liquid crystal forming lipids used in the aerosol is not limited to the following, but is generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and drugs and the propellant (the total weight of the external preparation; the same below), relative to the total weight of the aerosol raw materials filled in the container, usually 0.1w / w% or more, preferably 0.5w / w% or more, more preferably 1w / w% or more, for example, 1w / w% to 40w / w%, 3w / w% or more, 3w / w% to 40w / w%, 3w / w% to 20w / w%, 3w / w% to 15w / w%, 3w / w% to 10w / w%, 10w / w% to 30w / w% or 5w / w% to 9w / w%.

[0161] In one embodiment, the amount of the drug used in the aerosol is not limited to the following, but is generally 0.0001 w / w% or more, preferably 0.0005 w / w% to 5 w / w%, for example, 0.0005 w / w% to 1 w / w%, 0.001 w / w% to 1.5 w / w%, and preferably 0.0005 w / w% to 1.5 w / w%, for example, 0.0005 w / w% to 1.5 ...5 w / w% to 1.5 w / w%, and preferably 0.0005 w / w% to 1.5 w / w%, / w%~5w / w%, 0.001w / w%~10w / w%, 0.001w / w%~1w / w%, 0.001w / w%~0.1w / w%, 0.001w / w%~0.05w / w%, 0.001w / w%~0.01w / w%, 0.01w / w%~0.1w / w%, 0.1w / w%~3w / w% or 0.1w / w%~1w / w%.

[0162] In one embodiment, the amount of the propellant used in the aerosol is not limited to the following, but is generally 40 w / w% or more, preferably 50 w / w% or more, for example, 50 w / w% to 90 w / w%, 50 w / w% to 85 w / w%, 50 w / w% to 80 w / w%, 60 w / w% to 85 w / w%, 60 w / w% to 80 w / w%, 60 w / w% to 80 w / w%, 60 w / w% to 70 w / w% or 65 w / w% to 75 w / w%, relative to the total weight of the aerosol raw materials filled in the container.

[0163] In one embodiment, the amount of the aqueous medium used in the aerosol is not limited to the following, but is generally 0.1w / w% or more, preferably 0.5w / w% or more, more preferably 1w / w% or more, relative to the total weight of the aerosol raw materials filled in the container, and is generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and drugs and the propellant. For example, it is 3w / w% or more, 5w / w% or more, 0.1w / w% to 30w / w%, 1w / w% to 30w / w%, 3w / w% to 30w / w%, 3w / w% to 20w / w%, 3w / w% to 15w / w%, 1w / w% to 10w / w%, 3w / w% to 10w / w%, 5w / w% to 10w / w% or 5w / w% to 9w / w%.

[0164] In one embodiment, the weight ratio of the non-lamellar liquid crystal forming lipid to the aqueous medium may be preferably 1:5 to 5:1, 1:2 to 2:1, 1:1.5 to 1.5:1, for example, 1:1.3 to 1.3:1, 1:1.1 to 1.1:1, and in a preferred example, 1: 1. Alternatively, the weight ratio of the non-lamellar liquid crystal forming lipid to the aqueous medium may be 1:1 to 10:1 or 1.5:1 to 5:1, for example, 1:1, 1.5:1, 2:1, 3:1, 4:1 or 5:1.

[0165] The external preparation of the present invention formulated as an aerosol may or may not contain a surfactant. In one embodiment, the composition containing a non-lamellar liquid crystal forming lipid and a drug contains a surfactant. The surfactant is as described above. As a preferred example of a surfactant used in an aerosol, polyoxyethylene (196) polyoxypropylene (67) glycol (also known as Pluronic (R) F127, but is not limited thereto. In one embodiment, the amount of the surfactant used in the aerosol is not limited to the following, but is generally 0.01 w / w% or more, preferably 0.05 w / w% or more, more preferably 0.1 w / w% or more, for example, 0.05 w / w% to 15 w / w%, 0.1 w / w% to 5 w / w%, 0.3 w / w% or more, 0.3 w / w% to 10 w / w%, 0.3 w / w% to 2 w / w%, 0.3 w / w% to 1.5 w / w%, 0.3 w / w% to 1 w / w%, or 0.55 w / w% to 0.9 w / w%.

[0166] In one embodiment, the weight ratio of non-lamellar liquid crystal forming lipids to surfactants in the aerosol agent can preferably be 3:1 to 20:1, or 5:1 to 20:1, for example, it can be 3:1 to 11:1, 7:1 to 17:1 or 8:1 to 15:1, 8:1 to 13:1, 9:1 to 11:1, and in a preferred example it is 10:1.

[0167] The external preparation of the present invention formulated as an aerosol dosage form preferably further contains ethanol. The composition containing the non-lamellar liquid crystal forming lipid and the drug contains ethanol. By mixing ethanol, the skin permeability of the drug is further increased.

[0168] In one embodiment, the amount of ethanol used in the aerosol is not limited to the following, but relative to the total weight of the aerosol raw materials filled in the container, generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and drugs and the propellant, can be 1w / w% or more, preferably 3w / w% or more, for example, 5w / w% or more, 7w / w% or more, 1w / w% to 30w / w%, 1w / w% to 20w / w%, 5w / w% to 60w / w%, 5w / w% to 30w / w%, 5w / w% to 25w / w%, 7w / w% to 20w / w%, 10w / w% to 20w / w%, 13w / w% to 50w / w%, 13w / w% to 20w / w% or 15w / w% to 18w / w%.

[0169] In one embodiment, the amount of ethanol relative to the total weight (excluding propellant) of the composition containing non-lamellar liquid crystal forming lipids and the drug is not limited to the following, but can be, for example, 20w / w% to 60w / w% or 30w / w% to 50w / w%.

[0170] In one embodiment, the external preparation of the present invention formulated as an aerosol formulation may contain a drug, a non-lamellar liquid crystal forming lipid (for example, an amphiphilic compound represented by the general formula (I) or a glycerol fatty acid monoester, preferably mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol or mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol), a surfactant (preferably Pluronic (R)F127), ethanol and propellant (preferably LPG). In this case, the amount of ethanol may be as described above, but is preferably 5w / w% to 25w / w%, 13w / w% to 20w / w% or 15w / w% to 18w / w%, relative to the total weight of the aerosol raw materials filled in the container, generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and the drug and the propellant. In this case, the amount of propellant is preferably 50w / w% to 85w / w%, 60w / w% to 80w / w% or 60w / w% to 70w / w%, relative to the total weight of the aerosol raw materials filled in the container, generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and the drug and the propellant. In one embodiment, the amount of ethanol may be 5 w / w% to 25 w / w%, and the amount of the propellant may be 60 w / w% to 80 w / w%, relative to the total weight of the aerosol raw material filled in the container, generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and the drug, and the propellant. In one embodiment, the amount of ethanol may be 15 w / w% to 18 w / w%, and the amount of the propellant may be 60 w / w% to 70 w / w%, relative to the total weight of the aerosol raw material filled in the container, generally the total weight of the composition containing non-lamellar liquid crystal forming lipids and the drug, and the propellant.

[0171] The external preparation of the present invention formulated as an aerosol dosage form may also contain other ingredients. Such other ingredients are basically contained in the composition containing non-lamellar liquid crystal forming lipids and drugs. Regarding other ingredients, as described above for the external preparation of the present invention.

[0172] The aerosol can be manufactured using a technique known to those skilled in the art. In one embodiment, a non-lamellar liquid crystal-forming lipid, a drug, an aqueous medium, and, if necessary, a surfactant and other components are uniformly mixed, and ethanol is further added and mixed as needed to prepare a composition, and the aerosol stock solution is placed in a container, and then the container is filled with a propellant by using an air filling valve, etc., so that an aerosol can be manufactured. In another embodiment, a non-lamellar liquid crystal-forming lipid, a drug, and, if necessary, a surfactant and other components are uniformly mixed, and ethanol is further added and mixed as needed to prepare a composition as an aerosol stock solution.

[0173] By using the spray of such an aerosol agent, the drug-encapsulating liquid crystal is stably formed and attached to the application site on the biological surface, and has excellent drug permeability.

[0174] By applying the aerosol of the present invention to the biological surface of a subject (e.g., a mammal), preferably to the skin or mucous membrane (spray), the drug contained in the aerosol can be administered to the subject percutaneously or permucosally. Regarding the subject, as described above. The present invention also provides a method for administering or delivering such a drug.

[0175] 6. Liquid Crystal Precursor Preparation

[0176] The non-lamellar liquid crystal forming lipid of the topical preparation of the present invention may not form liquid crystal (non-lamellar liquid crystal) in the topical preparation. When the topical preparation of the present invention does not contain an aqueous medium or when the non-lamellar liquid crystal forming lipid does not contain an aqueous medium sufficient to form a liquid crystal, the non-lamellar liquid crystal forming lipid does not form a liquid crystal in the topical preparation. However, if such a topical preparation is applied to the surface of an organism in the presence of water, the non-lamellar liquid crystal forming lipid forms a liquid crystal on the surface of the organism and stably adheres to the surface of the organism. The present invention also provides the topical preparation of the present invention in which the non-lamellar liquid crystal forming lipid does not form a liquid crystal, i.e., a liquid crystal precursor preparation.

[0177] The external preparation of the present invention as a liquid crystal precursor preparation is preferably a composition containing non-lamellar liquid crystal forming lipids and a drug without containing an aqueous medium or containing a sufficient amount of an aqueous medium. The non-lamellar liquid crystal forming lipids, the drug and the aqueous medium are as described above.

[0178] In one embodiment, the amount of non-lamellar liquid crystal forming lipids used in the liquid crystal precursor preparation is not limited to the following, but can be 10 w / w% or more, preferably 30 w / w% or more or 50 w / w% or more, more preferably 60 w / w% or more, for example, 70 w / w% or more, 50 w / w% to 99.8 w / w% or more, 60 w / w% to 99.8 w / w% or more, 65 w / w% to 99.8 w / w%, 65 w / w% to 99.5 w / w%, 68 w / w% to 99 w / w%, 70 w / w% to 99.5 w / w% or 50 w / w% to 90 w / w% or 70 w / w% to 90 w / w%.

[0179] In one embodiment, the amount of the drug used in the liquid crystal precursor preparation is not limited to the following, but is generally 0.0001 w / w% or more, preferably 0.0001 w / w% to 10 w / w%, relative to the total weight of the liquid crystal precursor preparation (external preparation), for example, 0.0005 w / w% to 5 w / w%, 0.0005 w / w% to 1 w / w%, 0.001 w / w% to 5 w / w%, 0.001 w / w% to 1 w / w% or 0.001 w / w% to 0.1 w / w%.

[0180] The external preparation of the present invention as a liquid crystal precursor preparation preferably further contains a water-soluble polymer. The water-soluble polymer is as described above. Preferred examples of water-soluble polymers include hydroxypropyl cellulose (HPC), such as HPC-SSL, HPC-SL, HPC-L, HPC-M and HPC-H, but are not limited to these.

[0181] In one embodiment, the amount of the water-soluble polymer in the liquid crystal precursor preparation is not limited to the following, but is, for example, 0.01 w / w% or more, preferably 0.1 w / w% or more, for example, 0.1 w / w% to 10 w / w%, 1 w / w% to 5 w / w% or 0.5 w / w% to 2 w / w% relative to the total weight of the liquid crystal precursor preparation (external preparation).

[0182] The external preparation of the present invention as a liquid crystal precursor preparation may or may not contain ethanol. In one embodiment, the amount of ethanol in the liquid crystal precursor preparation is not limited to the following, but relative to the total weight of the liquid crystal precursor preparation (external preparation), it can be 1 w / w% or more, preferably 4 w / w% or more, for example, 5 w / w% to 40 w / w%, 5 w / w% to 30 w / w%, 10 w / w% to 30 w / w%.

[0183] The topical preparation of the present invention as a liquid crystal precursor preparation may or may not contain an oily component. As for the oily component, it is as described above. Preferred examples of oily components include: squalene, squalane, isopropyl myristate, tocopherol, etc., but are not limited to these. In one embodiment, the amount of the oily component in the liquid crystal precursor preparation is not limited to the following, but relative to the total weight of the liquid crystal precursor preparation (topical preparation), for example, 0.01w / w% or more, for example, 0.01w / w% to 60w / w%, 0.1w / w% to 40w / w%, 1w / w% to 30w / w%, 1w / w% to 10w / w% or 1w / w% to 8w / w%.

[0184] In one embodiment, the topical preparation of the present invention as a liquid crystal precursor preparation may contain a drug, a non-lamellar liquid crystal forming lipid (for example, an amphiphilic compound represented by the general formula (I) or a glycerol fatty acid monoester, preferably mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol or mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol), a water-soluble polymer (preferably hydroxypropyl cellulose) and ethanol.

[0185] The external preparation of the present invention as a liquid crystal precursor preparation may further contain other components. The other components are as described above with respect to the external preparation of the present invention.

[0186] The manufacture of the liquid crystal precursor preparation can be carried out using techniques known to those skilled in the art. The liquid crystal precursor preparation can be manufactured by fully mixing the above-mentioned raw materials. In one embodiment, the liquid crystal precursor preparation can be manufactured by fully mixing a water-soluble polymer, ethanol, and an oily component according to the situation in a non-lamellar liquid crystal forming lipid, adding a drug thereto and fully mixing. Alternatively, the liquid crystal precursor preparation can also be manufactured by fully mixing a drug, ethanol, and a water-soluble polymer and an oily component according to the situation, adding a non-lamellar liquid crystal forming lipid thereto and mixing. In addition, the liquid crystal precursor preparation can also be manufactured only by fully mixing non-lamellar liquid crystal forming lipids, pharmaceutical agents, water-soluble polymers, oily components, etc.

[0187] When such a liquid crystal precursor preparation is applied to the surface of a living body, in the presence of water, a liquid crystal encapsulating a drug is formed, which is stably attached to the application site and has excellent drug permeability.

[0188] The liquid crystal precursor preparation of the present invention can also be applied to the skin, but is more preferably applied to mucosa. By applying the liquid crystal precursor preparation of the present invention to mucosa, the non-lamellar liquid crystal forming lipid is contacted with water from the organism, and the self-formation of the liquid crystal (non-lamellar liquid crystal) formed by the non-lamellar liquid crystal forming lipid occurs on the mucosal surface. Thus, the liquid crystal of the encapsulated drug is stably attached to the mucosa, and has excellent drug mucosal permeability. Therefore, the present invention not only provides a preparation applied to the skin, but also provides a preparation applied to the mucosa. The external preparation of the present invention as a liquid crystal precursor preparation is particularly preferably applied to the mucosa.

[0189] By applying the liquid crystal precursor preparation of the present invention to the biological surface of an object (e.g., a mammal), preferably to a mucosa or skin (e.g., spraying, coating, dripping, etc.), the drug contained in the liquid crystal precursor preparation can be administered to the object through the mucosa or through the skin. When the liquid crystal precursor preparation of the present invention is applied to the skin, it is preferably applied to the skin moistened with an aqueous medium in advance or the aqueous medium is added to the preparation after the preparation is applied to the skin. Regarding the object and the aqueous medium, as described above. The present invention also provides a method for administering or delivering such a drug.

[0190] 7. External preparations containing microparticles

[0191] The present invention also provides an external preparation containing microparticles, wherein the microparticles contain the above-mentioned non-lamellar liquid crystal forming lipids and the above-mentioned drugs. The external preparation of the present invention can be a dispersion such as a dispersion (emulsion). The external preparation of the present invention can also contain a dispersion of microparticles, such as a dispersion (microparticle dispersion), wherein the microparticles contain non-lamellar liquid crystal forming lipids and drugs. The dispersion such as the dispersion preferably contains the above-mentioned non-lamellar liquid crystal forming lipids and the above-mentioned drugs in an aqueous medium such as water, and preferably contains a dispersant such as a surfactant. The dispersion such as the dispersion may also contain a solvent such as ethanol and / or an oily component according to the circumstances.

[0192] In the present invention, "microparticles" refer to particles having an average particle size of less than 1 mm. The "microparticles" of the present invention may be microparticles or nanoparticles. In the present invention, "microparticles" refer to particles having an average particle size of 1 μm or more and less than 1 mm. In the present invention, "nanoparticles" refer to particles having an average particle size of 1 nm or more and less than 1 μm. In the present invention, "dispersion" refers to any dispersion medium containing microparticles in a dispersed state. In the present invention, "microparticle dispersion" refers to a liquid medium containing microparticles in a dispersed state (for example, an aqueous medium such as water or a physiologically acceptable aqueous solution such as saline). "Microparticle dispersion" and "nanoparticle dispersion" refer to liquid media containing microparticles or nanoparticles in a dispersed state, respectively (for example, an aqueous medium such as water or a physiologically acceptable aqueous solution such as saline). The microparticles of the present invention, such as microparticles or nanoparticles, are composed of non-lamellar liquid crystal-forming lipids as the main component and may contain drugs inside them. Microparticles, such as microparticles or nanoparticles, can be prepared by dispersing a liquid crystal phase. In one embodiment, microparticles such as microparticles or nanoparticles can be prepared as a dispersion (emulsion) obtained as follows, wherein the dispersion (emulsion) is obtained by dispersing a suspension containing non-lamellar liquid crystal-forming lipids, drugs, aqueous media, surfactants and other dispersants and other components as needed by high-pressure dispersion, ultrasonic treatment, etc.

[0193] The non-lamellar liquid crystal forming lipid used in the preparation of microparticles may be any of the non-lamellar liquid crystal forming lipids described above. In one embodiment, the non-lamellar liquid crystal forming lipid may be an amphiphilic compound represented by the general formula (I), for example, mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol. In another embodiment, the non-lamellar liquid crystal forming lipid may be a glycerol fatty acid monoester, such as glycerol monooleate.

[0194] The microparticles may contain any of the above-mentioned drugs, but in one embodiment, they may be fat-soluble (lipophilic) drugs.

[0195] The "microparticles" of the present invention are not limited to the following, but preferably have an average particle size of 1 nm or more and less than 1 mm, for example, an average particle size of 1 nm to 500 μm, 10 nm to 500 μm, 50 nm to 500 μm, 10 nm to 1 μm, or 50 nm to 50 μm. The nanoparticles of the present invention are not limited to the following, but preferably have an average particle size of 1 nm to 500 nm, for example, an average particle size of 50 nm to 500 nm, 100 nm to 400 nm, or 100 nm to 300 nm.

[0196] The microparticle dispersions such as nanoparticle dispersions may contain any of the above-mentioned other components in addition to the non-lamellar liquid crystal forming lipids and the drug. In one embodiment, the microparticle dispersions such as nanoparticle dispersions also preferably contain any of the above-mentioned surfactants, for example, polyoxyethylene (196) polyoxypropylene (67) glycol (also known as Pluronic (R) In one embodiment, the microparticle dispersion such as nanoparticle dispersion can contain a solvent such as ethanol. In one embodiment, the microparticle dispersion such as nanoparticle dispersion can contain a surfactant and ethanol. In one embodiment, the microparticle dispersion such as nanoparticle dispersion can contain the above-mentioned oily component, the above-mentioned water-soluble organic compound and / or other pharmaceutically acceptable additives.

[0197] In one embodiment, the weight ratio of non-lamellar liquid crystal forming lipid to dispersant in a microparticle dispersion such as a nanoparticle dispersion is not limited to the following, but is preferably non-lamellar liquid crystal forming lipid: dispersant = 1:1 to 100:1, for example, it can be 3:1 to 50:1, 3:1 to 10:1, 5:1 to 40:1, 10:1 to 30:1, 10:1 to 25:1 or 15:1 to 25:1.

[0198] In one embodiment, when a solvent such as ethanol is used in a microparticle dispersion such as a nanoparticle dispersion, the weight ratio of the solvent such as ethanol to the non-lamellar liquid crystal forming lipid is not limited to the following, but is preferably non-lamellar liquid crystal forming lipid: solvent (e.g., ethanol) = 1:10 to 10:1, for example, it can be 1:1 to 10:1, 1.5:1 to 5:1, 2:1 to 10:1 or 5:1 to 10:1.

[0199] In one embodiment, the amount of the non-lamellar liquid crystal forming lipid, the drug, the dispersant (surfactant, etc.) and the solvent (ethanol, etc.) relative to the total weight of the microparticle dispersion such as the nanoparticle dispersion may be, for example, 1 w / w% to 40 w / w%, 0.001 w / w% to 10 w / w%, 0.05 w / w% to 15 w / w%, and 1 w / w% to 30 w / w%. In another embodiment, the amount of the non-lamellar liquid crystal forming lipid, the drug, the dispersant (surfactant, etc.) and the solvent (ethanol, etc.) relative to the total weight of the microparticle dispersion such as the nanoparticle dispersion may be, for example, 10 w / w% to 30 w / w%, 0.1 w / w% to 3 w / w%, 0.3 w / w% to 10 w / w%, and 1 w / w% to 20 w / w%.

[0200] In one embodiment, the amount of non-lamellar liquid crystal forming lipid, drug and dispersant (surfactant etc.) relative to the total weight of microparticle dispersion such as nanoparticle dispersion, for example, can be 1w / w% to 40w / w%, 0.001w / w% to 10w / w% and 0.05w / w% to 15w / w%. In another embodiment, the amount of non-lamellar liquid crystal forming lipid, drug and dispersant (surfactant etc.) relative to the total weight of microparticle dispersion such as nanoparticle dispersion, for example, can be 10w / w% to 30w / w%, 0.1w / w% to 3w / w% and 0.3w / w% to 10w / w%.

[0201] The topical preparation of the present invention containing the above-mentioned microparticles or microparticle dispersions can be any of the above-mentioned dosage forms. In one embodiment, the topical preparation of the present invention containing microparticles or microparticle dispersions can be applied to the biological surface of an object (e.g., a mammal), preferably applied to the skin or mucous membrane. In one embodiment, the topical preparation of the present invention containing microparticles or microparticle dispersions can be used for application to mucous membranes (mucosal surfaces), for example, can be a nasal agent. In another embodiment, the topical preparation of the present invention containing microparticle dispersions or microparticle dispersions can be a spray such as an aerosol agent.

[0202] 8. Intra-brain delivery

[0203] The topical preparation of the present invention can be particularly advantageously used for delivering drugs to the brain. In one embodiment, the topical preparation of the present invention for drug delivery in the brain can be a topical preparation containing the above-mentioned microparticles or microparticle dispersions. In one embodiment, the topical preparation of the present invention for application to mucosa (mucosal surface), such as the topical preparation of the present invention as a nasal preparation, is particularly suitable for delivering drugs to the brain. Such a topical preparation of the present invention can be a topical preparation of the present invention containing the above-mentioned microparticles or microparticle dispersions, and can also be the above-mentioned patch, aerosol agent, or liquid crystal precursor preparation. The topical preparation of the present invention can effectively deliver drugs to the brain by transdermal administration or transmucosal administration, such as intranasal administration. The topical preparation of the present invention can greatly improve the efficiency of drug delivery to the brain (especially including olfactory bulb, cortex, brainstem, cerebellum, midbrain and / or hippocampus).

[0204] Therefore, the present invention also provides a method for delivering a drug to the brain, the method comprising administering the topical preparation of the present invention to any object above-mentioned such as a person through the skin or through the mucosa, such as intranasal administration. Transdermal administration is not limited to the following, but can also be carried out using a patch, spray (aerosol, etc.), ointment or cream, etc. Transmucosal administration can also be carried out using a patch, spray (aerosol, etc.), nasal agent, oral agent, suppository or vaginal agent, etc.

[0205] The dosage of the topical preparation of the present invention for delivering drugs to the brain can be appropriately set by a person skilled in the art according to the drug. For example, the dosage of the topical preparation of the present invention is 1 ng to 10 g per kilogram of the subject's body weight, for example, 10 ng to 100 mg. For example, the dosage of the topical preparation of the present invention containing a microparticle dispersion is preferably 1 μL to 500 μL per kilogram of the subject's body weight, for example, 10 μL to 100 μL.

[0206] The drug contained in the external preparation for drug delivery in the brain can be any drug that is desired to be delivered in the brain, and can be an organic compound, an inorganic compound, a protein, a peptide, an amino acid, a nucleic acid, etc. The drug can be selected from the above-mentioned drugs. Examples of the drug include drugs for treating central nervous system diseases such as Alzheimer's disease, Parkinson's disease, cerebrovascular disorders, brain tumors, antipsychotic drugs, anesthetics, etc., but are not limited to these.

[0207] Example

[0208] The present invention will be further specifically described below using examples, but the technical scope of the present invention is not limited to these examples.

[0209] [Example 1] Synthesis of mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol

[0210] [Chemistry 6]

[0211]

[0212] 1.0 g (3.5 mmol) of 5,9,13-trimethyltetradec-4-enoic acid methyl ester (methyl tetrahydrofarnesyl acetate) was slowly added dropwise to a solution of 0.65 g (7.1 mmol) of glycerol and 0.59 g (4.3 mmol) of potassium carbonate in anhydrous N,N-dimethylformamide (3.5 mL) at 80°C. Stir at 100°C for 18 hours, then add 1 M hydrochloric acid to the reaction solution and extract with ether. The extract was washed with saturated sodium bicarbonate aqueous solution and saturated brine in sequence, dried over anhydrous sodium sulfate, filtered and concentrated. The residue was purified by silica gel column chromatography (ethyl acetate / hexane mixture) to obtain the title compound as a colorless transparent liquid.

[0213] For the obtained compound, 1 The results of H-NMR measurement and viscosity measurement are shown below.

[0214] 1 H-NMR spectrum (300 MHz, CDCl3, TMS) δ: 0.80-0.90 (m, 9H), 1.00-1.70 (m, 15H), 1.97 (td, J = 7.8, 17.0 Hz, 2H), 2.13 (t, J = 6.1 Hz, 1H, OH), 2.25-2.45 (m, 4H), 2.55 (d, J = 5.2 Hz, 1H, OH), 3.50-4.00 (m, 3H), 4.10-4.25 (m, 2H), 5.08 (t, J = 6.7 Hz, 1H) Viscosity: 0.48 Pa·s (shear rate 92 1 / s)

[0215] The synthesized mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol is also called C17MGE, or C17 glyceride.

[0216] [Example 2] Synthesis of mono-O-(5,9,13-trimethyltetradecanoyl)glycerol

[0217] [Chemistry 7]

[0218]

[0219] 70 g (0.53 mol) of 2,2-dimethyl-1,3-dioxolane-4-methanol and 36.7 g (266 mmol) of potassium carbonate were added to 50.3 g (177 mmol) of 5,9,13-trimethyltetradecanoic acid methyl ester, and stirred at 85°C for 3 hours under a reduced pressure of 200 mmHg to 250 mmHg. During this period, methanol generated in the reaction was distilled off. The obtained reaction solution was concentrated under reduced pressure (50°C → 210°C, 1.4 kPa → 0.38 kPa), and then purified by silica gel column chromatography (hexane / ethyl acetate) to obtain 43.0 g (yield 63%) of 5,9,13-trimethyltetradecanoic acid (2,2-dimethyl-1,3-dioxolane-4-yl) methyl ester.

[0220] To a solution of 32.7 g (85.0 mmol) of 5,9,13-trimethyltetradecanoic acid (2,2-dimethyl-1,3-dioxolan-4-yl) methyl ester in tetrahydrofuran (340 mL) was added 85 mL of 3M hydrochloric acid at room temperature, and stirred at the same temperature for 5 hours. The reaction solution was added to ethyl acetate (300 mL) and saturated sodium bicarbonate aqueous solution (400 mL) for separation. The obtained organic layer was washed with saturated brine and then dried over magnesium sulfate. The residue was obtained by filtration and concentration, and the residue was purified by silica gel column chromatography (hexane / ethyl acetate) to obtain 28.7 g (yield 98%) of the title compound, which was a colorless transparent liquid. For the obtained compound, the determination 1 The results of H-NMR are shown below.

[0221] 1 H-NMR spectrum (270MHz, CDCl3, TMS) δ: 0.7-0.9 (m, 12H), 0.95-1.45 (m, 16H), 1.45-1.75 (m, 3H), 2.34 (t, J=7.4Hz, 2H), 3.60 (dd, J=5.8, 11.5Hz, 1H), 3.70 (dd, J=4.0, 11.5Hz, 1H), 3.94 (m, 1H), 4.15 (dd, J=5.9, 11.7Hz, 1H), 4.21 (dd, J=4.7, 11.7Hz, 1H)

[0222] The synthesized mono-O-(5,9,13-trimethyltetradecanoyl)glycerol is also called saturated C17 glyceride.

[0223] [Example 3] Synthesis of mono-O-(5,9,13-trimethyltetradecano-4,8,12-trienoyl)glycerol

[0224] [Chemistry 8]

[0225]

[0226] Under a reduced pressure of 200 mmHg to 250 mmHg, 13.9 g (50.0 mmol) of 5,9,13-trimethyltetradec-4,8.12-trienoic acid methyl ester (methyl farnesyl acetate) was slowly added dropwise to a solution of 9.2 g (0.10 mol) of glycerol and 0.28 g (2.0 mmol) of potassium carbonate in anhydrous N,N-dimethylformamide (20 mL) at 85°C, and stirred at the same temperature for 3 hours. During this period, the methanol generated in the reaction was distilled off. The obtained reaction solution was diluted with an ethyl acetate / hexane mixed solvent (1:1, 150 mL), washed with water, saturated sodium bicarbonate aqueous solution, and saturated brine (2 times), and then dried over magnesium sulfate. The residue was obtained by filtration and concentration, and the residue was purified by silica gel column chromatography (hexane / ethyl acetate = 100:0 to 0:100) to obtain 8.22 g (yield 49%) of the title compound as a colorless transparent liquid. For the obtained compound, 1 The results of H-NMR measurement and viscosity measurement are shown below.

[0227] 1 H-NMR spectrum (270MHz, CDCl3, TMS) δ: 1.5-1.8 (m, 12H), 1.9-2.1 (m, 8H), 2.1 (brs, 1H, OH), 2.25-2.45 (m, 4H), 2.56 (brs, 1H, OH), 3.59 (dd, J=5 .6, 11.2Hz, 1H), 3.68 (dd, J=3.6, 11.2Hz, 1H), 3.92 (m, 1H), 4.14 (dd, J=6.0, 11.6Hz, 1H), 4.21 (dd, J=4.8, 11.6Hz, 1H), 5.02-5.16 (m, 3H)

[0228] Viscosity: 0.26 Pa·s (shear rate 92 1 / s)

[0229] The synthesized mono-O-(5,9,13-trimethyltetradec-4,8,12-trienoyl)glycerol is also called farnesyl acetate.

[0230] [Example 4] Synthesis of mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol

[0231] [Chemistry 9]

[0232]

[0233] Under reduced pressure of 60 mmHg to 70 mmHg and nitrogen flow, slowly add 28.2 g (80.0 mmol) of 5,9,13,17-tetramethyloctadec-4-enoic acid methyl ester to a solution of 23.5 g (255 mmol) of glycerol and 0.55 g (4.0 mmol) of potassium carbonate in anhydrous N,N-dimethylformamide (48 mL) at 80°C, and stir at the same temperature for 3 hours. Dilute the obtained reaction solution with a mixed solvent of ethyl acetate / hexane (1:1, 200 mL), wash with water, saturated sodium bicarbonate aqueous solution, and saturated brine (2 times), and then dry with magnesium sulfate. The residue is obtained by filtration and concentration, and the residue is purified by silica gel column chromatography (hexane / ethyl acetate = 100:0 to 30:70) to obtain 13.3 g (yield 40%) of the title compound as a slightly yellow transparent liquid. For the obtained compound, 1 The results of H-NMR measurement are shown below.

[0234] 1 H-NMR spectrum (300MHz, CDCl3, TMS) δ: 0.80-0.95 (m, 12H), 1.00-1.70 (m, 22H), 1.85-2.15 (m, 2H), 2.15-2. 55 (m, 4H), 3.53-3.78 (m, 3H), 3.80-4.00 (m, 1H), 4.10-4.25 (m, 2H), 5.08 (dd, J=6.9Hz, J=6.9Hz, 1H)

[0235] The synthesized mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol is also called C22MGE or C22 glyceride.

[0236] [Example 5] Synthesis of mono-O-(5,9,13,17-tetramethyloctadecanoyl)glycerol

[0237] [Chemistry 10]

[0238]

[0239] Under a nitrogen atmosphere, add 2.5 g of 5% palladium on carbon to a solution of 20.6 g (50.0 mmol) of mono-O-(5,9,13,17-tetramethyloctadec-4-enoyl)glycerol in ethyl acetate (62 mL). Replace the nitrogen in the reaction system with hydrogen, and then stir at room temperature for 42 hours under a normal pressure hydrogen atmosphere. Replace the hydrogen in the reaction system with nitrogen, and then filter out the 5% palladium on carbon. Purify the filtrate using silica gel column chromatography (ethyl acetate) to obtain 20.2 g (yield 98%) of the title compound, which is a colorless transparent liquid. For the obtained compound, 1 The results of H-NMR measurement are shown below.

[0240] 1 H-NMR spectrum (300MHz, CDCl3, TMS) δ: 0.7-0.9 (m, 15H), 0.95-1.75 (m, 26H), 2.13 (t, J=6.0Hz, OH), 2.34 (t, J=7.7Hz, 2H) , 2.56 (d, J=5.1Hz, OH), 3.55-3.75 (m, 2H), 3.94 (m, 1H), 4.15 (dd, J=6.0, 11.7Hz, 1H), 4.20 (dd, J=4.7, 11.7Hz, 1H)

[0241] The synthesized mono-O-(5,9,13,17-tetramethyloctadecanoyl)glycerol is also called saturated C22 glyceride.

[0242] [Example 6] Synthesis of mono-O-(5,9,13,17-tetramethyloctadecanoyl-4,8,12,16-tetraenoyl)glycerol

[0243] (1) Synthesis of 5,9,13,17-tetramethyloctadec-4,8,12,16-tetraenoic acid methyl ester (geranylgeranyl acetate methyl ester)

[0244] Under nitrogen atmosphere, a solution of 53 mL (0.42 mol) of trimethyl orthoacetate and 5.0 mL (40 mmol) of n-hexanoic acid was added dropwise at 135° C. to a solution of 58.1 g (200 mmol) of 3,7,11,15-tetramethylhexadec-1,6,10,14-tetraen-3-ol (geranyllinalool) and 19 mL (0.15 mol) of trimethyl orthoacetate over 8 hours. The mixture was stirred at the same temperature for 6 hours, and then a solution of 5.3 mL (42 mmol) of trimethyl orthoacetate and 0.5 mL (4 mmol) of n-hexanoic acid was further added dropwise, and the mixture was further stirred at the same temperature for 2 hours. The obtained reaction solution was diluted with a mixed solvent of ethyl acetate / hexane (3:1, 300 mL), washed with a saturated sodium bicarbonate aqueous solution (twice) and saturated brine, and then dried over magnesium sulfate. After filtration and concentration, 67.24 g of 5,9,13,17-tetramethyloctadec-4,8,12,16-tetraenoic acid methyl ester (geranylgeranyl acetate methyl ester) was obtained as a crude product liquid. The crude product was directly used in the next reaction.

[0245] (2) Synthesis of mono-O-(5,9,13,17-tetramethyloctadecyl-4,8,12,16-tetraenoyl)glycerol

[0246] [Chemistry 11]

[0247]

[0248] Under a reduced pressure of 200 mmHg to 250 mmHg, 13.9 g (40.0 mmol) of 5,9,13,17-tetramethyloctadec-4,8,12,16-tetraenoic acid methyl ester (geranylgeranyl acetate) was slowly added dropwise to a solution of 7.4 g (80 mmol) of glycerol and 5.5 g (40 mmol) of potassium carbonate in anhydrous N,N-dimethylformamide (16 mL) at 85°C, and stirred at the same temperature for 6 hours. During this period, the methanol generated in the reaction was distilled off. The obtained reaction solution was diluted with an ethyl acetate / hexane mixed solvent (1:1, 200 mL), washed with water, saturated sodium bicarbonate aqueous solution, and saturated brine (2 times), and then dried over magnesium sulfate. The residue was obtained by filtration and concentration, and the residue was purified by silica gel column chromatography (hexane / ethyl acetate = 100:0 to 0:100) to obtain 5.44 g (yield 33%) of the title compound as a transparent liquid. For the obtained compound, 1 The results of H-NMR measurement and viscosity measurement are shown below.

[0249] 1 H-NMR spectrum (270MHz, CDCl3, TMS) δ: 1.55-1.72 (m, 15H), 1.9-2.2 (m, 13H), 2.27-2.45 (m, 4H), 2.53 (brs, 1H, OH), 3.59 (dd, J=5.4, 11 .4Hz, 1H), 3.68 (dd, J=3, 11.4Hz, 1H), 3.92 (m, 1H), 4.15 (dd, J=6.0, 11.6Hz, 1H), 4.21 (dd, J=4.8, 11.6Hz, 1H), 5.05-5.15 (m, 4H)

[0250] Viscosity: 0.37 Pa·s (shear rate 92 1 / s)

[0251] The synthesized mono-O-(5,9,13,17-tetramethyloctadec-4,8,12,16-tetraenoyl)glycerol is also known as geranylgeranyl acetate.

[0252] [Example 7] Preparation of liquid crystal precursor preparation

[0253] 1. Reagents

[0254] Rhodamine B (RB) and triamcinolone acetonide (tA) were purchased from Wako Pure Chemical Industries, Ltd. (Osaka, Japan), and hydroxypropylcellulose (HPC) was purchased from Nippon Soda Co., Ltd. (Tokyo, Japan). The structural formula and physicochemical parameters of TA are shown in Table 1. ClogP as a hydrophobicity index was calculated using Chem Draw Ultra 10.0. (R)Calculations were performed by (PerkinElmer Informatics, Cambridge, MA, USA).

[0255] [Table 1]

[0256]

[0257] It is known that the viscosity of HPC increases with the average number of substituted hydroxyl groups (hydroxypropoxy groups) per cellulose (degree of substitution). HPC with a degree of substitution of 0.2% to 0.4% is called a low degree of substitution, and HPC with a degree of substitution of 53.4% ​​to 77.5% is called a high degree of substitution. Five grades of HPC are used, namely SSL, SL and L with low degrees of substitution, and M and H with high degrees of substitution. Among the viscosities (20°C, 2% aqueous solution) of these five types of HPC, SSL is 2 to 2.9 mPa·s, SL is 3 to 5.9 mPa·s, L is 6 to 10 mPa·s, M is 150 to 400 mPa·s, and H is 1000 to 4000 mPa·s.

[0258] 2. Preparation of Liquid Crystal Precursor Preparation (1)

[0259] The preparations containing RB or TA as drugs were prepared as follows.

[0260] First, add a small amount of HPC to a vial containing ethanol. Then, place the vial in a warm water bath set at 60°C and stir overnight to completely dissolve the HPC in the vial, thereby obtaining an ethanol solution containing HPC.

[0261] C17MGE was mixed with the HPC-containing ethanol solution obtained above at a weight ratio of 7:3 and stirred well for 1 hour. In addition, C17MGE and ethanol were added to a vial and mixed and stirred well to prepare a solution without HPC.

[0262] In the solution prepared as described above, RB was added to a final concentration of 0.001%, thereby preparing RB-containing preparations No. 1 to No. 6, and TA was added to a final concentration of 0.1%, thereby preparing TA-containing preparations No. 7 to No. 12. In addition, these preparations can also be prepared by adding the drug to an ethanol solution containing HPC or ethanol in advance, and then mixing with C17MGE.

[0263] In addition, in the absence of ethanol, by adding the drug and HPC to C17MGE and stirring, preparations No. 13 to No. 18 containing no ethanol but C17MGE were prepared.

[0264] Preparations No. 1 to No. 18 prepared as described above are liquid crystal precursor preparations that do not contain water.

[0265] Furthermore, as a comparative control, water was used instead of C17MGE, and ethanol, the drug, and HPC were mixed and stirred to prepare formulations No. 19 to No. 23 that did not contain C17MGE. In addition, an aqueous solution of No. 24 TA was prepared.

[0266] Table 2 shows the composition ratios (weight ratios) of the prepared preparations No. 1 to No. 24.

[0267] [Table 2]

[0268]

[0269]

[0270] 3. Preparation of Liquid Crystal Precursor Preparation (2)

[0271] Glycerol monooleate (GMO) was used instead of C17MGE in 2., and preparations No. 25 to No. 36 containing RB or TA were prepared according to the composition ratio (weight ratio) in Table 3 and the same operation steps as in 2. In addition, preparations No. 37 and No. 38 containing GMO without ethanol were prepared by adding the drug and HPC to GMO and heating and stirring in the absence of ethanol.

[0272] [Table 3]

[0273]

[0274] 4. Preparation of Liquid Crystal Precursor Preparation (3)

[0275] Using oily ingredients (squalene) + C17MGE, C22MGE, or oily ingredients (IPM or tocopherol) + C22MGE, according to the composition ratio (weight ratio) in Table 4 and following the same operating steps as in 2., preparations No. 39 to No. 49 and No. 79 to No. 81 containing RB or TA were prepared.

[0276] [Table 4]

[0277]

[0278]

[0279] [Example 8] Preparation property test

[0280] 1. Spray test

[0281] Preparations No. 1 to No. 5, No. 13, No. 19 to No. 23 and No. 46 prepared in Example 7 are added to a 5 mL spray bottle (No. 2, Maruemu Co., Ltd., Japan), and sprayed vertically downward once from a distance of 3 cm onto a Kimwipe paper moistened with water. The spray bottle used can manually spray about 60 μL at a time when purified water is used. The diameter of the area (spray area) where the preparation is sprayed on the Kimwipe paper is measured. If the spray can be sprayed and the diameter of the spray area is more than 1 cm, it is judged as a mist spray. If it is less than 1 cm, it is judged as a rod spray. If spraying is not possible from the injection port of the spray bottle, it is judged as not being able to spray.

[0282] As a result, when using the spray bottle, any of the preparations can be sprayed. Preparations No. 1, No. 19, and No. 20 are mist sprays, and preparations No. 2 to No. 5, No. 13, No. 21 to No. 23, and No. 46 are stick sprays.

[0283] 2. Liquid crystal structure formation test

[0284] In the same manner as in the spray test, a 5 mL spray bottle was used to spray the No. 1 to No. 5, No. 19, No. 25, and No. 26 formulations prepared in Example 2 vertically downward once from 15 cm from the bottom of a glass bottom petri dish (Matsunami Glass Industries, Ltd., Japan) into 150 μL of purified water dropped. In order to determine whether liquid crystals were formed, the formulations in contact with water in the petri dish were observed in polarized light microscopy mode using a digital microscope VHX-5000 (KEYENCE Co., Ltd., Japan).

[0285] Figure 1 The results of observation under a polarizing microscope are shown in FIG. In all of the preparations No. 1 to No. 5, No. 25, and No. 26 containing C17MGE or GMO, a polarizing image showing a liquid crystal structure ( Figure 1 A to E, G, H). However, in the preparation No. 19 containing HPC but not C17MGE, no polarized image showing the liquid crystal structure was confirmed ( Figure 1 F) indicates that the formulation containing C17MGE forms a liquid crystal structure in the sprayed water. In addition, the formulation using a lower degree of substitution of HPC has a clearer polarized image.

[0286] In addition, regarding C17MGE and GMO, the time from spraying to liquid crystal formation (forming a polarized image) was compared. The results showed that under the condition of no HPC, C17MGE No. 1 preparation was within 5 seconds, GMO No. 25 preparation was within 10 seconds, and under the condition of mixing HPC of the same grade SSL, C17MGE No. 2 preparation was within 20 seconds, GMO No. 26 preparation was within 90 seconds, and the liquid crystal formation of the preparations containing C17MGE (No. 1, No. 2) was significantly faster. The preparations containing either C17MGE and GMO were also quickly fixed on the mucosal surface after spraying, but the preparation containing C17MGE was more quickly and easily fixed on the mucosal surface after spraying than the preparation containing GMO, and it is believed that the effect of promoting the release and absorption of active ingredients is also more easily obtained.

[0287] 3. Small angle X-ray scattering diffraction

[0288] When the above-mentioned liquid crystal structure formation test was conducted using preparations No. 1 to No. 3, No. 13, No. 45 to No. 49 containing C17MGE or C22MGE and preparations No. 25 to No. 27 and No. 37 containing GMO, the preparations sprayed into water formed a gel-like substance. The gel-like substance was subjected to small-angle X-ray scattering (SAXS) diffraction measurement using a small-angle X-ray scattering (SAXS) device (Nano-Viewer manufactured by Rigaku Corporation) to determine the non-lamellar liquid crystal structure.

[0289] Small angle X-ray scattering diffraction ( Figure 2 A and D, and Figure 3 In A to D), at least three scattering peaks were observed, and the peak ratio showed a ratio unique to the reverse hexagonal phase liquid crystal. From this, it was confirmed that these preparations formed reverse hexagonal liquid crystals.

[0290] In addition, the small angle X-ray scattering diffraction ( Figure 2 In B, C, and E to G), at least six scattering peaks were observed, and the peak ratios showed a ratio unique to cubic liquid crystals belonging to the crystallographic space group Pn3m. The ratio is unique to the inverse hexagonal phase liquid crystal From this, it was confirmed that when these preparations were used, cubic liquid crystal and reverse hexagonal liquid crystal belonging to the crystallographic space group Pn3m were mixed and formed.

[0291] In the small angle X-ray scattering diffraction ( Figure 3 In E and F), at least eight scattering peaks were observed, and the ratio of the peaks showed a ratio unique to the anti-cubic liquid crystal belonging to the crystallographic space group Fd3m. From this, it was confirmed that these preparations formed anti-cubic liquid crystals belonging to the crystallographic space group Fd3m.

[0292] [Example 9] Preparation retention test on mucosa

[0293] Three mixed anesthetics (0.15 mg / kg of medetomidine hydrochloride, 2 mg / kg of midazolam, and 2.5 mg / kg of butorphanol tartrate) were intraperitoneally administered to WBN / ILA-Ht strain male hairless rats (200-250 g in weight, 8 weeks old), and the back skin was excised. The stratum corneum (horny layer) of the excised skin (3 cm × 3 cm) on the back of the rat was removed by tape stripping, and the obtained stratum corneum-peeled skin (skin with epidermis exposed) was used as a mucosal model.

[0294] The preparations No. 1 to 6, No. 13 to 17, No. 19 to 23, No. 25 to 28, No. 30, No. 39 to 41, No. 45 and No. 46 prepared in Example 7 were sprayed once vertically downward from a distance of 3 cm using a spray bottle. Immediately after spraying, the area of ​​the preparation attached to the mucosal model (= area just after spraying) was measured. 15 seconds after spraying, 37°C water was continuously flowed at a flow rate of 200 mL / min for 1 hour on the mucosal model tilted at a horizontal angle of 45°, and then the area of ​​the preparation attached to the mucosal model (= area after the water flow test) was measured. It should be noted that in the measurement of the area just after spraying and the area after the water flow test, a digital microscope VHX-5000 (KEYENCE Co., Ltd., Japan) with a stereo microscope mode equipped with a manual XY measurement system VH-M100 was used.

[0295] The reduction rate of the preparation adhesion area after the running water test was calculated according to the following formula.

[0296] Reduction rate (%) = (area after water flow test - area just after spraying) / area just after spraying × 100

[0297] When the reduction rate (%) is ≤ -50%, it is judged that the sample of the preparation has been peeled off from the mucosal model.

[0298] The flow test was performed three or more times on each preparation, and the preparation was divided into four groups according to the following criteria, and the preparation retention of each preparation was determined.

[0299] s: specimen without peeling;

[0300] a: The number of peeled samples accounts for less than 40% of the total number of samples;

[0301] b: The number of peeled specimens is greater than 40% and less than 70% of the total number of specimens;

[0302] c: The number of peeled samples accounts for more than 70% of the total number of samples.

[0303] For comparison, the commercially available oral mucosal adhesive preparation Aftach (R) (Teijin Pharma Ltd., Japan) 1 tablet or oral mucosal ointment preparation KENALOG (R) (Bristol-Myers Squibb Company, USA) 60 mg was attached or coated on the mucosal model, and the same running water test was performed. The results are shown in Table 5.

[0304] [Table 5]

[0305]

[0306]

[0307] As shown in Table 5, the preparations using C17MGE or C22MGE remained well after the 1-hour running water test, showing high mucosal adhesion. In particular, the preparations containing HPC and C17MGE or C22MGE showed very high mucosal adhesion (retention) and had higher mucosal adhesion than commercially available preparations. It should be noted that the ethanol solution containing HPC without using liquid crystal forming lipids was completely peeled off in the running water test.

[0308] [Example 10] Preparation retention test on skin

[0309] The running water test was performed in the same manner as in Example 9 except that Preparation No. 2 and Preparation No. 46 were used instead of the mucosal model (horny layer peeled skin) and the skin excised from the back of rats before tape peeling was used as a skin model.

[0310] The results showed that although both Preparation No. 2 and Preparation No. 46 were temporarily peeled off from the skin at the beginning of the running water test, the peeled gel reattached to the skin and fixed. It is believed that the reattachment to the skin surface was promoted by the entire preparation being in contact with water. This result shows that the preparation of the present invention is easy to peel off before forming liquid crystals on skin with little water (oily surface) and showing biological adhesion, but shows higher biological adhesion on skin with sufficient water.

[0311] [Example 11] In vitro release test

[0312] Xiang Ru Figure 4 The vertical diffusion unit shown (unit volume: 6.0 mL, effective diffusion area: 1.77 cm 2; Kobayashi Glass Co., Ltd.) was added with 6.0 mL of 20% ethanol aqueous solution, and a dialysis membrane (cellulose tube 24 / 32, Wako Pure Chemical Industries, Ltd., Japan) was set. Artificial saliva Saliveht was added to the dialysis membrane (supply unit side) (R) (Teijin Pharma Ltd., Japan) 200 μL, and then the preparation was applied to start the in vitro release test of the preparation.

[0313] As the preparations, preparations No. 7 to No. 12, No. 18, No. 24, No. 31 to No. 36, No. 38, No. 79, No. 80 and No. 81 (200 mg each) prepared in Example 7 containing 0.2 mg of TA as an active ingredient, KENALOG (R) Ointment preparation (200 mg) and Aftach (R) Preparation 1 tablet. Please note that KENALOG (R) The ointment preparation was applied according to the instructions for use after wiping off the artificial saliva on the dialysis membrane.

[0314] In order to determine the release of TA from the preparation, the aqueous solution in the receiving unit was sampled with 500 μL over time, and the same amount of 20% ethanol aqueous solution was added each time. The unit was maintained at 37°C and stirred with a magnetic stirrer. During the test, the vertical diffusion unit was set in a high humidity environment maintained at a humidity of more than 90% using a humidifier.

[0315] Acetonitrile was added to each sample solution collected over time at a ratio of 1:1 (v / v), stirred, and centrifuged (21,500×g, 5 minutes, 4°C) to recover the supernatant. The supernatant was measured by high performance liquid chromatography (HPLC) to determine the TA concentration. The HPLC system and conditions used in this measurement are shown in Tables 6 and 7.

[0316] [Table 6]

[0317] HPLC system (Shimadzu Corporation, Kyoto, Japan)

[0318] System Controller SCL-10A Pump LC-10AD Autosampler SIL-10A Column oven CTO-10AC UV detector SPD-10AV Analysis software LC solution Degassing device DGU-12A3

[0319] [Table 7]

[0320] HPLC assay conditions

[0321]

[0322] Table 8 shows the effective diffusion area (1.77 cm) of the unit calculated from the measured value of TA concentration. 2 ), the cumulative release of TA per unit effective release area after 4 hours of application of the preparation (μg / cm 2, the average of more than 3 tests), and KENALOG (R) Relative release compared to ointment formulations.

[0323] [Table 8]

[0324]

[0325] Formulations containing C17MGE, GMO, or C22MGE showed similar performance to the commercially available KENALOG (R) The ointment preparations had substantially the same TA release. In addition, among the preparations containing C17MGE, the preparations containing HPC (Nos. 8 to 12, 18) showed a tendency to have higher TA release than the preparation not containing HPC (No. 7).

[0326] [Example 12] In vitro mucosal permeability test

[0327] As in Example 11, a vertical diffusion unit (unit volume: 6.0 mL, effective diffusion area: 1.77 cm 2 )( Figure 4 ) was added to the receiving unit of the dialysis unit, and 6.0 mL of phosphate buffered saline (PBS) at pH 6.75 was added to replace the dialysis membrane used in Example 11, and the oral mucosa of hamsters (Syrian (male, 8 weeks old), Sankyo Laboratory Service Co., Ltd.) was set. Artificial saliva Saliveht was added to the oral mucosa (supply unit side) (R) (Teijin Pharma Ltd., Japan) 200 μL, and then the assay was started using the preparation.

[0328] As the preparations, preparations No. 7, No. 8, No. 24, No. 31 to No. 33, No. 38 and No. 80 (200 mg each) prepared in Example 7 containing 0.2 mg of TA as an active ingredient, KENALOG (R) Ointment preparation (200 mg) and Aftach (R) Preparation 1 tablet. In addition, KENALOG (R) The ointment preparation is applied according to the instructions for use after wiping off the artificial saliva on the oral mucosa.

[0329] In order to measure the mucosal permeation of TA from the preparation, 500 μL of the aqueous solution in the receiving unit was sampled over time, and the same amount of PBS was added each time. The unit was maintained at 37°C and stirred with a magnetic stirrer. The vertical diffusion unit was set up in a high humidity environment maintained at a humidity of more than 90% using a humidifier to conduct the test.

[0330] Acetonitrile was added to each sample solution collected over time at a ratio of 1:1 (v / v), stirred, and centrifuged (21,500×g, 5 minutes, 4°C) to recover the supernatant. The supernatant was measured by high performance liquid chromatography (HPLC) to determine the TA concentration. The HPLC system and conditions used in this measurement are shown in Tables 6 and 7.

[0331] Figure 5 The mucosal permeation behavior of TA from each evaluation preparation is shown in the figure. The vertical axis of the figure represents the calculated value of TA concentration based on the unit effective diffusion area (1.77 cm 2 ) per effective permeation area (μg / cm 2 ) (average of more than 3 tests).

[0332] Table 9 shows the cumulative mucosal permeation of TA per unit effective permeation area 4 hours and 8 hours after application of the preparation and the difference with KENALOG (R) Relative permeation compared to ointment preparations.

[0333] [Table 9]

[0334]

[0335] Preparations 7, 8, 31-33, 38 and 80 all showed high mucosal permeability. In particular, preparations 8 and 80 containing C17MGE or C22MGE and HPC showed high mucosal permeability compared with commercially available mucosal preparations (Aftach (R) 、KENALOG (R) ) also showed significantly higher mucosal permeability than the control group, indicating that the mucosal absorbability of the active ingredient was greatly improved.

[0336] In addition, the relative permeation amounts of the No. 8 and No. 80 preparations after 4 hours were greater than the relative permeation amounts after 8 hours, and the drug could be delivered more effectively in a shorter time.

[0337] From these results, it is understood that the preparation containing the liquid crystal forming lipid of the present invention and a water-soluble polymer such as HPC not only exhibits high mucosal adhesion and skin adhesion, but also has high drug mucosal permeability and can significantly improve drug mucosal absorbability.

[0338] [Example 13] Preparation of spray

[0339] C17MGE as a liquid crystal forming lipid was mixed with Pluronic F-127 and mixed with a vortex mixer for 5 minutes. Then, a fluorescein sodium (FL-Na) aqueous solution with a concentration of 790 μg / g was added and homogenized (8000 rpm, 5 minutes) using a high-speed disperser (POLYTRON PT-3100, KINEMATICA, Switzerland) to prepare a liquid crystal gel (Preparation No. 58). The composition of the liquid crystal forming lipid in Preparation No. 58: Pluronic F-127: FL-Na aqueous solution = 1:0.1:1 (weight ratio). The FL-Na concentration in Preparation No. 58 is 376 μg / g.

[0340] Ethanol was added to Preparation No. 58 at a ratio of Preparation No. 58: ethanol = 1:0.5 or 1:1 (weight ratio), and the resulting solution was mixed with a vortex mixer for 5 minutes. The solution was filled in a manual 5 mL spray bottle (No. 2, Maruemu Co., Ltd., Japan), thereby preparing No. 50 and No. 51 pump sprays, respectively.

[0341] In addition, aerosols No. 52 and No. 53 were prepared by adding No. 50 or No. 51 (solution) to an aerosol container (Daizō Co., Ltd., Japan), installing a liquefied petroleum gas (LPG) filling valve, and filling the container with LPG as a propellant. The composition of No. 52 was No. 50:LPG = 1.5:4 (weight ratio). The composition of No. 53 was No. 51:LPG = 1:2 (weight ratio).

[0342] In addition, sprays No. 54 to No. 57 were prepared according to the same composition and method as those of preparations No. 50 to No. 53, except that C22MGE was used instead of C17MGE.

[0343] The FL-Na concentration in preparations No. 50 to No. 57 was set to 376 μg / g, similar to preparation No. 58, when all ethanol and LPG were volatilized after spraying.

[0344] As a comparative control, Preparation No. 59 (FL-Na concentration: 376 μg / g) in which FL-Na aqueous solution and ethanol were mixed at a weight ratio of 1:1, and Preparation No. 60 (FL-Na concentration: 376 μg / g) as a 1 mM FL-Na aqueous solution were prepared.

[0345] Table 10 shows the composition ratios (weight ratios) of preparations No. 50 to No. 60.

[0346] [Table 10]

[0347]

[0348] [Example 14] Test on properties of spray

[0349] 1. Spray test

[0350] The aerosols No. 52, No. 53, No. 56 and No. 57 prepared in Example 13 were shaken 5 times just before spraying and then sprayed vertically downwards onto the glass surface from a distance of 10 cm.

[0351] For these aerosol agents, the spray amount at each spray time was calculated per second over a period of 1 to 5 seconds. The results were expressed as approximate values ​​of the spray amount per second (g / sec). The values ​​for preparation No. 52 were 0.723 g / sec, for preparation No. 53 were 0.868 g / sec, for preparation No. 56 were 0.726 g / sec, and for preparation No. 57 were 0.711 g / sec.

[0352] Preparations No. 52, No. 53, No. 56, and No. 57 were all sprayed in a very fine mist. Thus, ethanol evaporated instantly, and the sprayed preparations were fixed on the glass surface without flowing down after spraying for 1 second and tilting the glass surface 45 degrees after 60 seconds.

[0353] However, when 0.19 g, 0.29 g, 0.19 g, and 0.24 g of LPG-free pump sprays No. 50, No. 51, No. 54, and No. 55 were sprayed, respectively, when the glass surface was tilted 45 degrees after 60 seconds, all of the four sprayed preparations flowed down on the glass surface.

[0354] The aerosol preparation of the present invention shows that it does not flow down from the application site immediately after spraying, and the preparation can be applied very effectively.

[0355] 2. Determination of particle size distribution

[0356] The spray of the present invention can form nanoparticles immediately after spraying.

[0357] The compositions obtained by spraying No. 50 to No. 57 sprays into a beaker for 1 second were diluted about 1000 times with distilled water as measurement samples, and the particle size distribution and zeta potential representing the particle surface charge were measured by dynamic light scattering using Zetasizer Nano-ZS (manufactured by Malvern).

[0358] Table 11 shows the average particle size (nm) (Z-average), PdI (polydispersity coefficient), and zeta potential (mV) obtained as the average of three measurements. All of the emulsions were shown to be in good condition.

[0359] [Table 11]

[0360]

[0361] 3. Small-angle X-ray diffraction

[0362] Aerosol agents No. 52, 53, 56 and 57 were sprayed into a centrifuge tube for 3 seconds respectively, and then 5 mL of purified water was added to obtain a composition, which was packaged in a labeled tube and subjected to small-angle X-ray scattering (SAXS) measurement using a small-angle X-ray scattering (Nano-Viewer) device (manufactured by Rigaku Corporation) to determine the non-lamellar liquid crystal structure.

[0363] In the small angle X-ray scattering diffraction ( Figure 6 In A, C, and D), at least three scattering peaks were observed, and the ratio of the peaks showed a ratio unique to the reverse hexagonal phase liquid crystal. From this, it was confirmed that these samples formed reverse hexagonal liquid crystals.

[0364] In addition, in the small angle X-ray scattering diffraction ( Figure 6 In B), at least 8 scattering peaks were observed, and the ratio of the peaks showed a ratio unique to cubic liquid crystals belonging to the crystallographic space group Pn3m. The ratio is unique to the inverse hexagonal phase liquid crystal Thus, it was confirmed that the sample was formed by a mixture of cubic liquid crystal and inverse hexagonal liquid crystal belonging to the crystallographic space group Pn3m.

[0365] Furthermore, a white sample obtained by spraying the No. 56 preparation on a petri dish for 1 second and then leaving it for about 3 minutes was directly inserted into the pinhole slit and subjected to the same small-angle X-ray scattering diffraction measurement to determine the non-lamellar liquid crystal structure. As a result, at least three scattering peaks were observed, and the ratio of the peaks showed a ratio unique to the inverse hexagonal phase liquid crystal. ( Figure 6 E) Thus, it was confirmed that the sample formed a reverse hexagonal liquid crystal.

[0366] These aerosols appear to be capable of forming non-lamellar liquid crystal structures, whether or not additional water is added after spraying.

[0367] [Example 15] In vitro skin permeability test

[0368] Three mixed anesthetics (0.15 mg / kg of medetomidine hydrochloride, 2 mg / kg of midazolam, and 2.5 mg / kg of butorphanol tartrate) were intraperitoneally administered to WBN / ILA-Ht male hairless rats (weight 200-250 g, 8 weeks old), and the abdominal skin was shaved. A total of four pieces (2 cm × 2 cm each) were cut out from the midline, and the subcutaneous fat and blood on the dermis side were carefully removed with scissors to prepare the abdominal skin of the rats.

[0369] As in Example 11, a vertical diffusion unit (unit volume: 6.0 mL, effective diffusion area: 1.77 cm 2 )( Figure 4 ) was added with 6.0 mL of phosphate buffer (PB) at pH 7.4 to the receiving unit, and the above rat abdominal skin was set instead of the dialysis membrane used in Example 11. 1.0 mL of PB was added to the stratum corneum (supply unit side) and hydrated for 1 hour, and then the measurement was started using the preparation.

[0370] As the preparations, preparations No. 50 to No. 53 and No. 56 to No. 60 prepared in Example 13 were used. The application amount of the preparations was 0.218 g (containing 54 μg of FL-Na) for preparation No. 50, 0.290 g (containing 54 μg of FL-Na) for preparation No. 51, 0.723 g (containing 49 μg of FL-Na) for preparation No. 52 after spraying for 1 second, 0.868 g (containing 54 μg of FL-Na) for preparation No. 53 after spraying for 1 second, 0.726 g (containing 49 μg of FL-Na) for preparation No. 56 after spraying for 1 second, 0.711 g (containing 44 μg of FL-Na) for preparation No. 57 after spraying for 1 second, 0.145 g (containing 54 μg of FL-Na) for preparation No. 58, 1 mL (containing 376 μg of FL-Na) for preparation No. 59, and 1 mL (containing 376 μg of FL-Na) for preparation No. 60.

[0371] In order to measure the amount of FL-Na permeated through the skin from the preparation, 500 μL of the aqueous solution in the receiving unit was sampled over time and the same amount of PB was added each time. The unit was maintained at 32°C and stirred with a magnetic stirrer.

[0372] Each sample solution collected over time was centrifuged (21,500×g, 5 minutes, 4° C.), and then the supernatant was measured using a fluorescence spectrophotometer (RF-5300PC: Shimadzu Corporation, Japan) (excitation wavelength: 485 nm, fluorescence wavelength: 535 nm) to determine the FL-Na concentration in the sample solution.

[0373] Figure 7 The skin permeation behavior of FL-Na from each preparation is shown. The vertical axis of the graph represents the calculated value of FL-Na concentration based on the unit effective diffusion area (1.77 cm 2 ) per effective permeation area per unit area of ​​FL-Na (μg / cm 2 ) (the average value of 3 or 4 test values).

[0374] Table 12 shows the cumulative skin permeation amount of FL-Na per unit effective permeation area 4 hours and 8 hours after application of the preparations and the relative permeation amount compared with Preparation No. 60 (control).

[0375] [Table 12]

[0376]

[0377] Sprays No. 50 to No. 53, No. 56, and No. 57 all showed significantly higher skin permeability than FL-Na aqueous solution (Preparation No. 60), further liquid crystal gel (Preparation No. 58), and 50% ethanol aqueous solution (Preparation No. 59). The cumulative skin permeation of FL-Na of pump spray No. 50 and No. 51 after 4 hours of application was 27 times and 184 times higher than that of preparation No. 60, respectively. Moreover, the cumulative skin permeation of FL-Na of aerosol No. 52, No. 53, No. 56, and No. 57 after 4 hours was 104 times, 345 times, 33 times, and 138 times higher than that of preparation No. 60, respectively. In addition, the cumulative skin permeation of FL-Na after 8 hours of application also showed a high value with the same trend.

[0378] As shown in Example 14, aerosols No. 52, 53, 56, and 57 do not flow down from the application site immediately after spraying, and can be applied more effectively than pump sprays No. 50 and 51 that do not contain LPG. If the above is taken into consideration at the same time, it is shown that they can be further used as extremely useful skin permeation promoting preparations.

[0379] [Example 16] Preparation of rubber patch preparation

[0380] C17MGE, phytantriol (PHY, Tokyo Chemical Industry Co., Ltd., Japan) or C22MGE as liquid crystal forming lipids and FL-Na aqueous solution in which FL-Na is dissolved in phosphate buffer (PB) at pH 7.4 are filled into a gas-tight syringe (mS-GAN025, Ito Seisakusho Co., Ltd., Japan) at a weight ratio of 1:1, 2:1, and 3:1, respectively, and mixed uniformly to obtain a liquid crystal gel. The FL-Na concentration of the FL-Na aqueous solution is set to make the FL-Na concentration of the final adhesive layer described later to be 10mM. It should be noted that since PHY is a semisolid at room temperature, it is used after being melted with a heating stirrer (100°C, 30 minutes).

[0381] Adding acrylic adhesive DURO-TAK to liquid crystal gel (R) (387-2516, Henkel, Germany) was mixed with a magnetic stirrer (500 rpm, 5 minutes) to make the weight ratio 80% relative to the whole adhesive layer. The mixture was placed on the backing of a silicone-processed polyethylene terephthalate (PET) film (FILMBYNA(R) 75E-0010BD, Fujimori Industry Co., Ltd., Japan), and a No. 510 BAKER film applicator (Yasuda Seiki Co., Ltd., Japan) with a set film thickness of 1 miL (25.4 μm) was used to extend from the left end (0%) to the right end (100%). Figure 8 The stretched adhesive layer was dried in a room at a temperature of 20±2°C and a humidity of 20±5% for 30 minutes, and further dried in an incubator at a temperature of 32°C and a humidity of 20±2% for 30 minutes. The dried adhesive layer was crimped onto a PET film support (FILMBYNA (R) , Fujimori Industries, Ltd., Japan), and rubber patch preparations (preparations No. 61 to 69) were prepared therefrom.

[0382] Table 13 shows the final composition ratio (weight ratio) in the adhesive layer of Preparation Nos. 61 to 69.

[0383] [Table 13]

[0384]

[0385] In addition, by the same method as above, according to the composition ratio (weight ratio) shown in Table 14, a liquid crystal forming lipid (C17MGE) and the above-mentioned acrylic adhesive (pressure-sensitive adhesive) DURO-TAK in a weight ratio of 90%, 70%, and 20% were prepared. (R) The rubber patch preparations No. 70 to No. 72 obtained by mixing, and the preparation of the acrylic adhesive DURO-TAK without mixing with liquid crystal forming lipids and mixing with a weight ratio of 90% (R) The obtained rubber patch preparation No. 73.

[0386] [Table 14]

[0387] Preparation No. 70 71 72 73 Code T-D90M5 T-D70M15 T-D20M40 T-D90M0 C17MGE 5 15 40 PHY C22MGE DURO-TAK 90 70 20 90 FL-Na aqueous solution 5 15 40 10 total 100 100 100 100

[0388] [Example 17] Characteristic test of rubber patch preparation

[0389] 1. Image Analysis

[0390] In Example 16, the rubber patch preparations No. 61 to No. 73 after the adhesive layer was dried and before the PET film support was pressed, were usually photographed and imaged under a fluorescence microscope.

[0391] The images usually taken were obtained by photographing the entirety of each rubber patch preparation from 20 cm above using a digital camera (D5300, Nikon Corporation, Japan).

[0392] Fluorescence microscopy images were obtained using a fluorescence microscope (BZ-X700, KEYENCE Co., Ltd., Japan) by photographing the area 25% ( Figure 8 Position 1), 50% ( Figure 8 Position 2), 75% ( Figure 8 The conditions for photographing under the fluorescence microscope were as follows: objective lens CFI Plan Apoλ2x, fluorescence filter GFP (OP-87763 BZ-X filter), excitation wavelength 470 / 40nm, absorption wavelength 525 / 50nm, dichroic mirror wavelength 495nm, gain +6dB. It should be noted that the exposure time was set to 1 / 175s for the preparation containing liquid crystal-forming lipids and 1 / 5s for the preparation not containing liquid crystal-forming lipids.

[0393] Mixing weight ratio of 80% and 90% DURO-TAK (R) The adhesive layers of the rubber patches No. 61 to No. 70 were uniformly extended. (R) The adhesive layer of the rubber patch No. 71 was slightly less uniform than that of No. 61 to No. 70. In addition, 20% by weight of DURO-TAK (R) The rubber patch No. 72 preparation is mixed with 90% by weight of DURO-TAK without mixing with liquid crystal forming lipids. (R) The adhesive layer of the rubber patch No. 73 preparation was not evenly extended.

[0394] From this result, it is found that by mixing DURO-TAK at a certain weight ratio or more, (R) (preferably 70% or more, more preferably 80% or more) and the liquid crystal-forming lipid of the present invention, a uniform rubber patch preparation can be prepared.

[0395] 2. Thickness of adhesive layer

[0396] The thickness of the entire rubber patch preparation was measured using a hand clipper (thickness gauge, Teclock Co., Ltd., Japan), and the thickness of the support (20 μm) and backing (80 μm) was subtracted from the measured value to calculate the thickness of the adhesive layer of the rubber patch preparation.

[0397] From the left center of No. 63, No. 66, and No. 69 preparations ( Figure 8 ) to 25%( Figure 8 Position 1), 50% ( Figure 8 Position 2), 75% ( Figure 8 The thickness of the adhesive layer at three locations (positions) was 15±5 μm (average value of 6 measurements).

[0398] This confirmed that the thickness of the adhesive layer of the rubber patch preparation was uniform.

[0399] 3. Analysis of phase diagram

[0400] The rubber patch preparation was observed for shape using a scanning probe microscope (SPM-9700HT, Shimadzu Corporation, Japan) with observation fields of 1 μm×1 μm and 0.5 μm×0.5 μm, and then for phase observation.

[0401] The shape of the preparations No. 63 and No. 73 was observed, and smooth surface shapes were observed. In addition, the phase of these preparations was observed, and the results were as follows: Fig. 9 As shown, no phase pattern was observed in Preparation No. 73, while a characteristic phase pattern was observed in Preparation No. 63.

[0402] The results show that the physical properties of the adhesive layer surface are different depending on the presence or absence of mixed liquid crystal forming lipids. (R) The rubber patch preparation has characteristic surface properties on a structure with a certain regularity.

[0403] [Example 18] In vitro release test

[0404] Xiang Ru Fig.10 The horizontal diffusion unit shown (unit volume: 3.0 mL, effective diffusion area: 0.95 cm 2 PB 3.0 mL was added to the receiving unit of the Kobayashi Glass Co., Ltd., and the preparation was attached to the supply unit side to start the in vitro release test of the preparation. As the preparation, preparations No. 61 to No. 69 and No. 73 were used.

[0405] In order to measure the amount of FL-Na released from the preparation, 500 μL of the aqueous solution in the receiving unit was sampled over time, and the same amount of PB was added each time. The unit was maintained at 32°C and stirred with a magnetic stirrer.

[0406] Each sample solution collected over time was centrifuged (21,500×g, 5 minutes, 4° C.), and then the supernatant was measured using a fluorescence spectrophotometer (RF-5300PC: Shimadzu Corporation, Japan) (excitation wavelength: 485 nm, fluorescence wavelength: 535 nm) to determine the FL-Na concentration in the sample solution.

[0407] Fig.11 The release behavior of FL-Na from each preparation is shown in the figure. The vertical axis of the figure represents the average value (average value of 3 or 4 test values) of the cumulative release rate (%) of FL-Na based on the extraction test calculated from the measured value of FL-Na concentration.

[0408] The cumulative release rate (%) of FL-Na 1 hour and 4 hours after application of the preparation is shown in Table 15. The cumulative release rate (%) of FL-Na was calculated according to the following formula.

[0409] FL-Na cumulative release rate (%) = FL-Na cumulative release amount ÷ FL-Na application amount × 100

[0410] [Table 15]

[0411]

[0412] Preparations No. 61 to No. 69 all released FL-Na rapidly over time. In particular, preparations No. 62, 63, 65, and 66 showed a higher cumulative release rate after 1 hour of application, and reached a release rate close to 100% after 4 hours of application. In particular, preparations No. 62 and 63 reached a release rate close to 100% after 1 hour of application, and released FL-Na very rapidly.

[0413] However, the rubber patch No. 73 formulation without liquid crystal lipids slowly released FL-Na, reaching a release rate of about 25% 4 hours after application, after which no release of FL-Na was observed. This showed that the encapsulated drug could not be effectively released without liquid crystal lipids.

[0414] [Example 19] In vitro skin permeability test

[0415] According to the method described in Example 15, the vertical diffusion unit ( Figure 4 Preparations No. 61 to 69 were applied to the stratum corneum of the abdominal skin of rats (supply unit side) and an in vitro skin permeation test was performed. In addition, as a comparative control, a 10 mM FL-Na aqueous solution No. 74, which was prepared by dissolving FL-Na in PB, was used.

[0416] Fig.12 The skin permeation behavior of FL-Na from each preparation is shown in the figure. The vertical axis of the figure represents the average value (average value of 3 or 4 test values) of the cumulative skin permeation rate (%) of FL-Na based on the extraction test calculated from the measured value of FL-Na concentration.

[0417] The cumulative skin permeation rate (%) of FL-Na at 1 hour and 4 hours after application of the preparation is shown in Table 16. The cumulative release rate (%) of FL-Na was calculated according to the following formula.

[0418] FL-Na cumulative release rate (%) = FL-Na cumulative permeation / FL-Na application amount × 100

[0419] [Table 16]

[0420]

[0421] The skin permeability of rubber patch preparations No. 61 to 69 was significantly improved compared with the FL-Na aqueous solution preparation No. 74. Moreover, compared with the rubber patch preparations No. 64 to 66 containing PHY, the skin permeability of preparations No. 61 to 63 containing C17MGE was very high. Considering that there was little difference in in vitro release between the rubber patch preparations containing C17MGE or C22MGE and the rubber patch preparations containing PHY in Example 18, the high skin permeability shown by the rubber patch preparations containing C17MGE or C22MGE was an unexpected result. Moreover, 4 hours after application and 4 hours later, the skin permeability of preparations No. 62 to 63 was improved by more than what was expected based on the content ratio of liquid crystal forming lipids compared with preparation No. 61 ( Fig.12 ).

[0422] [Example 20] Preparation of emulsion

[0423] According to the mixing ratio (weight ratio) shown in Table 17, C17MGE or glycerol monooleate (GMO, RIKEMAL XO-100, NOF) as a liquid crystal forming lipid, Tranilast (Tokyo Chemical Industry Co., Ltd., Japan) as a drug, and ethanol (only No. 76) were mixed and dissolved in a hot water bath at 80°C. Pluronic (R) F127(UNILUBE (R) 70DP-950B, NOF, or Aldrich P2443) dissolved in purified water, and after adding the aqueous solution, stirred with a spoon or a vortex mixer to prepare a suspension. In addition, the suspension was ultrasonically treated with an ultrasonic disperser (Sonics Vibra-Cell VCX-750, manufactured by Sonics & Materials, Inc.) at an amplitude of 20% for 5 minutes to prepare white emulsions No. 75 to No. 77 containing microparticles. These emulsions were prepared in an amount of 10 g each. It should be noted that tranilast is known to be an antiallergic agent, but its therapeutic effect on nervous system diseases has also been studied (US 2011 / 0112187 A1).

[0424] In a 20% lipid emulsion, C17MGE can be used in a 1% amount of Pluronic (R) F127 is dispersed, but GMO cannot be dispersed. Therefore, GMO is dispersed in 5% Pluronic (R)As a comparative control, preparation No. 78 was prepared in which 0.5% of tranilast was added to physiological saline (Table 17).

[0425] [Table 17]

[0426]

[0427] [Example 21] Evaluation of physical properties of emulsion

[0428] The particle size distribution and small angle X-ray scattering diffraction of emulsions No. 75 to No. 77 prepared in Example 20, as well as the viscosity of emulsions No. 75 and No. 76 and the encapsulation efficiency of tranilast were measured.

[0429] The particle size distribution was measured by a dynamic light scattering method using a Zetasizer Nano-ZS (manufactured by Malvern). The measurement samples were prepared by diluting each emulsion 1000 times in distilled water. For each measurement sample, the average particle size (nm) (Z-average), PdI (polydispersity coefficient) and zeta potential (mV) obtained as the average of 3 measurements are shown in Table 18.

[0430] Each emulsion was stable with no visible agglomerates throughout the experiment, as evidenced by the moderate average particle size, PdI and zeta potential.

[0431] The small angle X-ray scattering diffraction was measured by sealing each emulsion in a labeled tube using a small angle X-ray scattering (SAXS) apparatus (Nano-Viewer manufactured by Rigaku Corporation).

[0432] Small angle X-ray scattering diffraction (SAXSD) of No. 75 emulsion Fig.13 In A), at least three scattering peaks are observed, and the ratio of the peaks shows a ratio unique to the reverse hexagonal phase liquid crystal. This showed that the present emulsion was a liquid crystal emulsion (hexosome) in which fine particles of reverse hexagonal liquid crystal were dispersed in an aqueous phase.

[0433] In addition, the small angle X-ray scattering diffraction ( Fig.13 In B), at least four scattering peaks were observed, and the ratio of the peaks showed a ratio unique to cubic liquid crystals belonging to the crystallographic space group Pn3m. This shows that the present emulsion is a liquid crystal emulsion (cubosome) in which cubic liquid crystal particles belonging to the crystallographic space group Pn3m are dispersed in an aqueous phase.

[0434] In addition, the small angle X-ray scattering diffraction ( Fig.13C), at least three scattering peaks were observed, and the peak ratio showed a ratio unique to cubic liquid crystals belonging to the crystallographic space group Im3m. This shows that the present emulsion is a liquid crystal emulsion (cubosome) in which microparticles of cubic liquid crystal belonging to the crystallographic space group Im3m are dispersed in an aqueous phase.

[0435] The viscosity was measured using a viscometer (RE215H; cone-plate type 0.8° x R24, Toki Sangyo Co., Ltd.) at a temperature of 25°C and a rotation speed of 50 rpm. The viscosity (mPa·s) is shown in Table 18. All of these viscosities were within the sprayable range.

[0436] To calculate the encapsulation efficiency, each emulsion was centrifuged (21,500×g, 15 minutes, 4° C.), and the resulting supernatant was taken out and diluted 10-fold with acetonitrile, and tranilast was quantified by liquid chromatography tandem mass spectrometry (LC-MS / MS). The encapsulation efficiency was calculated according to the following formula.

[0437] [Number 1]

[0438]

[0439] In the above formula, %EE, TL 总 TL 游离 They represent the encapsulation efficiency, the total tranilast concentration in the emulsion, and the tranilast concentration in the supernatant, respectively.

[0440] As shown in Table 18, the encapsulation efficiency of each emulsion was high, indicating the high absorption capacity of tranilast into the liquid crystal structure inside the microparticles.

[0441] [Table 18]

[0442]

[0443] [Example 22] In vitro release test

[0444] Xiang Ru Figure 4 The vertical diffusion unit shown (unit volume: 6.0 mL, effective diffusion area: 1.77 cm 2 ; Kobayashi Glass Co., Ltd.) was added with 6.0 mL of phosphate buffered saline (PBS; pH 7.4), and a dialysis membrane (molecular weight cutoff = 12,000-14,000 Da, Sanko Pure Chemical Industries, Ltd., Japan) pre-soaked in water was set. The preparation was applied to the dialysis membrane (supply unit side) and the in vitro release test of the preparation was started. As the preparation, 1 mL of each of the emulsion preparations No. 75 and No. 76 and the comparative control preparation No. 78 were used.

[0445] In order to measure the release amount of Tranilast from the preparation, 500 μL of the aqueous solution in the receiving unit was sampled over time, and the same amount of PBS was added each time. The unit was maintained at 32° C. and stirred with a magnetic stirrer.

[0446] Acetonitrile was added to each sample solution collected over time at a ratio of 1:1 (v / v), stirred, and centrifuged (21,500×g, 5 minutes, 4°C) to collect the supernatant. 10 μL of the supernatant was injected into the LC / MS / MS system to quantify Tranilast.

[0447] The LC / MS / MS system used in this measurement is composed of the following: system controller (CBM-20A, Shimadzu Corporation), pump (LC-20AD, Shimadzu Corporation), autosampler (SIL-20ACHT, Shimadzu Corporation), column oven (CTO-20A, Shimadzu Corporation), mass spectrometer (4000QTRAP, AB SCIEX), and analysis software (Analyst (registered trademark) version 1.4.2, Shimadzu Corporation).

[0448] The measurement conditions of LC / MS / MS are as follows: the chromatographic column (Shodex ODP2HPG-2A 2.0 mm×10 mm, Showa Denko K.K.) was maintained at 40°C. The mobile phase was acetonitrile: 5 mM ammonium acetate aqueous solution containing 0.05% formic acid = 80:20. The flow rate was maintained at 0.2 mL / min. Mass spectrometry was performed in the multiple reaction monitoring (MRM) mode, and the transition ions from m / z 328.0 to m / z 191.2 were monitored at a collision energy of 36 eV.

[0449] Fig.14 The release behavior of tranilast from each preparation within 8 hours after application is shown in FIG. The vertical axis of the graph represents the cumulative release amount of tranilast (μmol / cm 2 ) is the average value (average of 4 test values).

[0450] The release behavior of tranilast from each preparation was closely related to the Higuchi equation (Higuchi T., J. Pharm. Sci., 52, 1145-1148 (1963)). Fig.14 Calculated release rate of tranilast (μmol / cm 2 / h 0.5 ) was as high as 0.17 in Preparation No. 76, and was 0.05 in Preparations No. 75 and No. 78. Fig.14The calculated cumulative tranilast release rate (%) after 8 hours of application of the formulations was 1.82, 3.67, and 2.35, respectively, for formulations 75, 76, and 78. Formulations 75 and 76 having tranilast encapsulated in a liquid crystal structure showed clear release properties.

[0451] [Example 23] Pharmacokinetic evaluation of intranasal administration

[0452] Sprague-Dawley rats (male 7 weeks old, weight 230 g ± 10 g) were used to evaluate the pharmacokinetics of intranasal administration of preparations No. 75 to 78. First, three mixed anesthetics (0.375 mg / kg of medetomidine hydrochloride, 2.5 mg / kg of butorphanol tartrate, and 2 mg / kg of midazolam) were administered intraperitoneally to the rats for general anesthesia. The tip of the micropipette was inserted 0.5 cm into the nostrils of the rats in the supine position, and 10 μL of the preparation was dripped, thereby performing intranasal administration.

[0453] At predetermined time points (0.17 hours, 0.5 hours, 1 hour, 2 hours, 4 hours and 8 hours after administration), about 200 μL of blood was collected from the jugular vein of the rat, directly transferred to a heparinized tube, and immediately centrifuged (21,500×g, 10 minutes, 4°C) to obtain plasma. Each time blood was collected, an equal amount of physiological saline was injected into the rat through the tail vein. In some rats, after 2 hours, 4 hours or 8 hours of administration, three mixed anesthetics were intraperitoneally administered, general anesthesia was implemented, and cardiopulmonary perfusion was performed with cold PBS, and the rat brain was cut out. The cut brain was dissected on ice in specific areas (olfactory bulb, cortex, brainstem, cerebellum, midbrain, hippocampus). The spinal cord was also collected from the dead rat. The collected brain sample was weighed, then cut with scissors, 0.5 mL of acetonitrile was added, and homogenized at 12,000 rpm for 5 minutes at 4°C using a disperser (POLYTRON PT1200E, KINEMATICA, Switzerland). The brain homogenate was centrifuged (21,500×g, 5 min, 4° C.) and the supernatant was recovered. The supernatants obtained from plasma and brain homogenate were stored at −30° C. before analysis.

[0454] Acetonitrile was added to 50 μL of the supernatant obtained from plasma or brain homogenate at a ratio of 1:1 (v / v), stirred, and centrifuged (21,500×g, 5 minutes, 4° C.) to recover the supernatant. 10 μL of the obtained supernatant was injected into the LC / MS / MS system in the same manner as in Example 22 to quantify tranilast.

[0455] Fig.15 and Fig.16The graph shows the temporal changes in plasma and brain tranilast concentrations within 8 hours after intranasal administration of each preparation. The vertical axis of the graph shows the average value (average value of 3 to 5 test values) of tranilast concentration (ng / mL or ng / g).

[0456] based on Fig.15 , Fig.16 The results shown were used to determine the time to maximum concentration (Tmax), maximum concentration (Cmax), and area under the drug concentration-time curve (AUC) as pharmacokinetic parameters of tranilast in plasma and brain within 8 hours after intranasal administration of each preparation. 0-8 ). These values ​​are shown in Table 19.

[0457] [Table 19]

[0458]

[0459] * For plasma, ng / mL; for brain, ng / g

[0460] ** For plasma it is ng.h / mL, for brain it is ng.h / g

[0461] The Tmax in plasma was 0.17 hours after the first blood sampling after intranasal administration for both emulsions No. 75 to 77 and control preparation No. 78, indicating rapid systemic absorption. The Tmax in the brain was 2 hours after the first blood sampling after intranasal administration for control preparation No. 78, and 8 hours after intranasal administration for emulsions No. 75 to 77.

[0462] In plasma, Cmax was not significantly different between emulsions No. 75 and No. 76 using C17MGE and the control preparation No. 78, but AUC of No. 75 and No. 76 was 0-8 It is more than 3 times higher than that of No. 78. In addition, in the brain, the Cmax of No. 75 and No. 76 is about 8 times higher than that of No. 78, and the AUC of No. 75 and No. 76 is 0-8 However, compared with the control preparation No. 78, the Cmax and AUC in plasma of the emulsion No. 77 using GMO were significantly higher than those of the control preparation No. 78. 0-8 were lower, but in the brain Cmax and AUC 0-8 Both are about 5 times higher.

[0463] As described above, in emulsions No. 75 and No. 76 using C17MGE, tranilast was detected at high concentrations in both plasma and brain, which were higher than the concentrations shown in emulsion No. 77 using GMO. In addition, it is particularly noteworthy that the concentration of tranilast in the brain was significantly increased in emulsions No. 75 and No. 76 compared with No. 78. From this, it can be seen that the emulsion using C17MGE is excellent in delivering drugs to the brain through intranasal administration.

[0464] Fig.17 and Fig.18 The tranilast concentrations in different brain regions 2 hours, 4 hours, and 8 hours after intranasal administration of each preparation are shown in the figure. The vertical axis of the figure represents the average value of the tranilast concentration (ng / g) (the average value of 3 to 5 test values).

[0465] Emulsions No. 75-77 and the comparative control formulation No. 78 all showed absorption of tranilast starting 2 hours after first excision in all brain regions. Among all brain regions, tranilast concentrations from these formulations were generally higher in the olfactory bulb and spinal cord than in other brain regions ( Fig.17 , 18 ). Since the olfactory bulb is adjacent to the nasal cavity and the spinal cord is the entrance of the systemic pathway to the brain, this result indicates that the brain migration of Tranilast occurs via both the olfactory pathway and the systemic pathway.

[0466] In all brain regions, tranilast concentrations from emulsions 75 and 76 using C17MGE were generally higher within 8 hours after intranasal administration and significantly higher after 8 hours of intranasal administration compared with emulsion 77 using GMO and control formulation 78 ( Fig.17 , 18 ). It can be seen that compared with emulsion No. 77 and control preparation No. 78, the high concentration of tranilast in emulsions No. 75 and No. 76 accumulated in the entire brain area for a long time.

[0467] Industrial Applicability

[0468] According to the present invention, an external preparation excellent in drug absorbability in a living body can be provided.

[0469] All publications, patents and patent applications cited in this specification are incorporated herein by reference as if they were directly incorporated into this specification.

Claims

1. Use of a non-lamellar liquid crystal forming lipid in the preparation of an external preparation for application to mucosa, the external preparation containing a non-lamellar liquid crystal forming lipid, a drug and hydroxypropyl cellulose, the external preparation being a liquid crystal precursor preparation, the non-lamellar liquid crystal forming lipid not forming liquid crystals in the external preparation, and the non-lamellar liquid crystal forming lipid being mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol or a salt thereof.

2. The use according to claim 1, wherein Topicals also contain oily ingredients.

3. The use according to claim 1 or 2, wherein Topicals also contain ethanol.

4. Use of non-lamellar liquid crystal forming lipids in the preparation of an external preparation for application to mucosa, the external preparation containing non-lamellar liquid crystal forming lipids, drugs, surfactants and water, the external preparation being an emulsion containing microparticles, the microparticles containing the non-lamellar liquid crystal forming lipids and the drugs, the non-lamellar liquid crystal forming lipids being mono-O-(5,9,13-trimethyltetradec-4-enoyl)glycerol or a salt thereof.

5. The use according to claim 4, wherein Topicals are used for drug delivery into the brain via intranasal administration.

6. The use according to claim 5, wherein The surfactant is a block copolymer of ethylene oxide and propylene oxide.

Citation Information

Patent Citations

  • Coloring curable resin composition

    JP2018168365A

  • Use Of Tranilast And Derivatives Thereof For The Therapy Of Neurological Conditions

    US20110112187A1

  • Type ii cubic liquid crystal composition

    WO2006043705A1

  • Low-viscosity liquid-crystal compound

    WO2011078383A1

  • Adhesion preventing agent

    WO2014178256A1